3D seismic imaging of a fracture damage zone controlling reservoir compartmentalization at the Raft River EGS using multi-azimuth walkaway VSP - Benxin Chi; Kai Gao; David Li; Joseph Moore; Clay Jones; Lianjie Huang (Geothermics, 2026)

Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Proceedings from Nourish Now: A science dialogue on improving adolescent health through nutrition - Mario G. Ferruzzi; Regan L. Bailey; Teresa A. Davis; Heather J. Leidy; Jamie I. Baum; Jill Castle; Angela De Leon; Eva C. Diaz; Victor L. Fulgoni; Carolyn Gunther; Leslie Kaplan; Bracha Kopstick; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Neutral lipid fatty acid composition in the epidermis and blubber of long-finned pilot whales (Globicephala melas) in the Northeast Atlantic confirms tissue-specific stratification - Anna Sophie Kebke; Tessa Plint; Sascha K. Hooker; Clayton R. Magill; David J. Moore; Andrew Brownlow (Marine Biology, 2026)
Fatty acid profiling is a widely used tool in cetacean dietary and health assessments, yet most studies focus exclusively on blubber, overlooking the epidermis – the largest organ and primary barrier against environmental stressors – which remains largely uncharacterised, despite its accessibility for sampling of live and deceased animals. Here, we present a comparative analysis of fatty acid composition across the epidermis and the outer and inner blubber layer of long-finned pilot whales ( Globicephala melas ). Gas chromatography-mass spectrometry on total lipid extracts identified several major lipid classes in the cetacean epidermis: free fatty acids (~ 25%), wax and steryl esters (~ 40%), and triacylglycerols (~ 30%). Monounsaturated fatty acids (MUFAs) dominated (> 59%) across the layers. Polyunsaturated fatty acids (PUFAs), generally linked to dietary intake, were more abundant in the inner blubber layer, while saturated fatty acids (SFAs) were highest in the epidermis. Inter-layer differences in abundance of 29 out of 34 (~ 85%) identified fatty acids were statistically significant, confirming tissue-specific stratification and that epidermal and blubber fatty acid profiles are not equivalent for current fatty acid dietary analyses. The distinct fatty acid composition of the epidermis suggests roles in antimicrobial defence and thermal regulation, indicating its potential as a biomarker for monitoring the health of cryptic cetacean species under changing environmental conditions. These findings establish a baseline knowledge of the neutral lipid fatty acid profile in cetacean epidermis and reaffirm the continued importance of blubber rather than skin biopsies for dietary assessments.

Beneficial use of contaminated sediments: a literature review of the state of practice in Europe and North America - John Toll; Eric Hedblom; Luca Sittoni; Arjan Widjeveldt; David Moore; Clifford Firstenberg; Steven Brown; Eric Dott (Journal of Soils and Sediments, 2026)

Adaptation and Response in Drylands: A Dryland Research Agenda and Campaign Strategy - Andrew F. Feldman; Sasha C. Reed; Konrad Wessels; Dennis Ojima; David J. P. Moore; William K. Smith; Niall P. Hanan; Cibele Amaral; Flurin Babst; Joel A. Biederman; Marcy Litvak; Natasha MacBean; et al. (Global Change Biology, 2026)
Dryland ecosystems cover 41% of Earth's land surfaces, account for 44% of cultivated lands and 60% of food sources, and make large contributions to the global water and carbon cycles. However, these ecosystems are experiencing unprecedented extremes including heatwaves, floods, and droughts as well as hotter temperatures and often declining water resource availability. These ecosystems are some of the most challenging to monitor given their high temporal variability with rapid response to their environment as well as vast spatial variability with intermixing of different plant species and life forms amongst bare soil coverage. The Adaptation and Response in Drylands (ARID) campaign was selected by National Aeronautics and Space Administration (NASA) as a scoping study to develop a research agenda for a dryland field campaign. Here, we detail our ARID science research agenda and implementation plan that were developed based on an extensive community engagement effort in over 160 events with over a thousand scientists, land managers, and Tribal communities between 2023 and 2024. The selected science themes cover drought and climate variability, ecosystem structure, function, and biodiversity, carbon cycle interannual variability and trends, and social ecological systems (land management and adaptation). We then detail our remote sensing, modeling, and field‐based strategies to capture high temporal and high spatial resolution processes. Finally, our implementation strategy is presented which includes focus area selections in a core intensive western U.S. domain and distributed international domains. This strategy includes our overarching guiding principles of using multi‐temporal airborne acquisitions and super sites as well as enhancing land management in co‐development with end‐user partners. While originally developed for NASA, our ARID report creates a blueprint for any future dryland field campaign, at any scale, that can be implemented widely for foundational and applied science objectives.

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Toward an integrated understanding of animal weapons - Christine W. Miller; Dominic Cram; Sarah M. Lane; Romain Boisseau; Sophia Fitzgerald; Nicole Lopez; Allen J. Moore; Christina J. Painting; Alexandre V. Palaoro; Michael Ryan; Ummat Somjee; Camille Thomas-Bulle; et al. (Trends in Ecology & Evolution, 2026)

Drinking Water Hardness (as a Proxy for Calcium) Significantly Modifies the Relationship Between Dental Caries Prevalence in 5 Year Old Children and Drinking Water Fluoride and Socio-economic Inequalities in England - Mohammad Mehrabi; Yang Han; Deborah Moore; Matthew J. Ascott; Anne-Marie Glenny; David A. Polya (Exposure and Health, 2026)
Dental caries (DC) is the most prevalent chronic disease. Previous studies have revealed negative associations between DC prevalence and both drinking water fluoride concentration (F) and socioeconomic status but further predictors, notably drinking water calcium, have been little explored, particularly in the UK. Therefore, this study employed multiple linear regression (MLR) to model the dependency of children’s DC on all three of these predictors, namely (i) F, (ii) IMD: index of multiple deprivation, and (iii) WH: water hardness—as a proxy for calcium concentration; in England. The results showed that all three predictors are statistically significantly (p < 0.05) associated with DC, with, separately, increased fluoride, increased water hardness, and decreased deprivation being associated with lower DC. A key novel finding is that the DC ~ F relationship is quantitatively less pronounced (by about 24%) when WH is included as a predictor—thus the oral health and financial benefits of water fluoridation based on models not considering water calcium may overestimate or underestimate those benefits depending upon water calcium (or WH as a proxy). Moreover, segmented analyses showed that, potentially and partially due to WH’s influence, the DC ~ F relationship is dependent upon F concentration, with the dependence much stronger for drinking water F < 0.10 mg/L than for F > 0.37 mg/L, a concentration considerably lower than the widely reported optimal F, i.e., (0.7–1.0) mg/L. Any modelling of expected costs and benefits for fluoridation should explicitly include consideration of water calcium (or WH as proxy) and the non-first-order linear DC ~ F relationship.

Characterizing Airborne Particulate Matter During Late-Season Soybean Production Using SEM/EDX Automated Single Particle Analyses and Machine Learning: A Preliminary Study in the Mississippi Delta - Matthew T. Moore; Lucas J. Heintzman; Juanita Rausch; David Jaramillo-Vogel; Martin A. Locke (Bulletin of Environmental Contamination and Toxicology, 2026)

Proximal measurements of microwave reflectance using GNSS-IR track semi-arid grassland vegetation dynamics during greening and browning phases - Charles J. Devine; Russell L. Scott; Joel A. Biederman; Jinyang Du; David J.P. Moore; Andrew F. Feldman; Jessicca S. Guo; David K. Adams; William K. Smith (Agricultural and Forest Meteorology, 2026)

Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

A cross-cohort comparison of the prevalence and clinical significance of Alzheimer’s disease biomarkers in people with versus without HIV - Lillian Ham; Olivia Villers; Judith D. Lobo; Tyler R. Bell; Debralee Cookson; Douglas Galasko; Scott L. Letendre; Mark W. Bondi; David J. Moore; Erin E. Sundermann (Journal of NeuroVirology, 2026)
With over half of people with HIV (PWH) in the U.S. entering older adulthood, identifying markers to distinguish Alzheimer’s disease (AD) and its precursor, amnestic mild cognitive impairment (aMCI), from other forms of neurocognitive impairment among PWH is urgent. We examined how HIV and aMCI status relate to AD CSF biomarkers in adult PWH and people without HIV (PWoH) characterized for aMCI. We included 80 PWH from the National NeuroHIV Tissue Consortium and 80 PWoH from the Wisconsin Registry for Alzheimer’s Prevention. Binary logistic regressions of AD-related CSF biomarker positivity (Aβ 42, Aβ 42 /Aβ 40, t-tau, p-tau 181 , Aβ 42 /t-tau) were conducted with HIV serostatus, aMCI status, HIV x aMCI interaction, and demographic covariates. Among PWH, we examined how HIV-disease characteristics relate to AD biomarker positivity. No HIV x aMCI interactions were detected. Regardless of aMCI status, having HIV was associated with higher odds of CSF Aβ 42 (OR = 7.97) and Aβ 42 /Aβ 40 (OR = 6.06) positivity, suggesting increased cerebral Aβ plaque burden. Regardless of HIV serostatus, having aMCI was associated with higher odds of CSF p-tau 181 positivity (OR = 3.64). Neither HIV nor aMCI status related to Aβ 42 /t-tau positivity. No HIV-disease characteristics related to AD biomarker positivity. Higher CSF Aβ positivity in PWH versus PWoH, regardless of aMCI status, suggests that HIV disease promotes amyloidosis; however, whether positive CSF biomarkers in PWH raises risk for future cognitive impairment and AD remains to be explored longitudinally. Like PWoH, elevated CSF p-tau 181 among PWH may indicate increased risk for AD-related memory impairment.

Conservation management on an Oregon livestock ranch supports net soil carbon and nitrogen storage - Samuel W. Valliere; David E. Prado-Tarango; Jennifer M. Moore; Serkan Ates; Ricardo Mata-González (Agriculture, Ecosystems & Environment, 2026)

Success of restoration strategies in preventing extirpation of 2 critically endangered coral species - Erinn M. Muller; Mark C. Ladd; Richard Karp; Phanor H. Montoya‐Maya; Ilsa B. Kuffner; Andrew C. Baker; Erich Bartels; Amanda Bourque; Abigail S. Clark; Nikkie Cox; Martine D'Alessandro; Ben Daughtry; et al. (Conservation Biology, 2026)
An unprecedented marine heatwave in 2023 caused widespread coral bleaching and mortality throughout the Caribbean. In the Florida Keys (USA), 2 foundation species, elkhorn coral ( Acropora palmata ) and staghorn coral ( Acropora cervicornis ), were severely affected. These species have been the primary focus of reef restoration in Florida for decades. Substantial losses of these species occurred in outplanted populations, in ocean‐based nurseries, and among remnant wild colonies, leading to uncertainty over their future in the Florida Keys, given recent observed trends in climate conditions. However, the past 2 decades of restoration activity created a community of experts, a network of ocean‐based and land‐based coral‐rearing infrastructure, and 2 independent land‐based coral gene banks that prevented regional extirpation and preserved much of the genetic richness of these critically endangered coral species. Without the past decades of effort and the emergency response associated with the 2023 bleaching event, Florida acroporids would largely have been lost. This outcome afforded by the restoration network in Florida demonstrates the value of proactively establishing resources prior to major disturbances. We identified several critical strategies that, in the context of existing climate change, are preventing the extirpation of coral species in Florida, including extending collaborative restoration efforts to solidify a network of trained experts; establishing trust‐focused relationships among management agencies and restoration groups; testing direct interventions to reduce light and temperature stress early during thermal anomalies; developing redundant ocean‐based and land‐based nurseries; and establishing living coral gene banks prior to major threats to prevent the extirpation of coral species.

Food Substitution and Waste Reduction Can Reduce the Environmental Impacts and Food Costs of School Meal Programs in the United States: An 2011-2018 NHANES Analysis - David C. Love; Zach Conrad; Daphene Altema-Johnson; Rebecca Ramsing; Karen Bassarab; Andrew L. Thorne-Lyman; D’Ann L. Williams; E.R.H. Moore; Elizabeth M. Nussbaumer; Patti Truant Anderson (Journal of the Academy of Nutrition and Dietetics, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Satellite observations reveal ecosystem resistance and resilience to short-term water stress driven by dominant vegetation along a rainfall gradient in Australia - Huanhuan Wang; Qiaoyun Xie; Sally E. Thompson; Caitlin E. Moore; David L. Miller; Erik J. Veneklaas; Richard P. Silberstein; Xing Li; Jingfeng Xiao; Belinda E. Medlyn; William K. Smith (Remote Sensing of Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Spatiotemporal Patterns and Drivers of Fish Biodiversity on a Remote Freshwater Archipelago - David J. Gallagher; Mark C. Romanski; Jay D. Glase; Seth A. Moore; Courtney E. Larson; Donn K. Branstrator; Thomas R. Hrabik (Journal of Biogeography, 2026)
Aim Fish communities are shaped by environmental filters operating across different spatiotemporal scales. While many recent studies focus on anthropogenic gradients, few can isolate the role of natural drivers in community assembly. Isle Royale's inland lakes offer a rare opportunity to explore long‐term fish biodiversity dynamics with minimal confounding influences. We analysed fish communities in 23 lakes surveyed in the 1920s, 1990s, and 2020s to 1) assess temporal changes in richness and composition 2) identify lakes and species experiencing the greatest change, and 3) evaluate environmental drivers of community structure. Location Isle Royale National Park, USA. Taxon Freshwater fish. Methods We analysed historical and contemporary fish survey data using species‐area curves, PERMANOVA, and multivariate dispersion tests to quantify changes in richness and composition, temporal beta diversity indices and similarity percentages (SIMPER) to identify lakes and species changing most, and non‐metric multidimensional scaling (NMDS) to examine relationships with environmental factors. Results Mean richness and species‐area curve slopes declined slightly but non‐significantly over time. Community composition remained largely stable with no homogenization, although subtle shifts from cold‐water to cool‐water species were observed in larger lakes. Species gains and losses were associated with isostatic rebound rate. Fast‐rebounding lakes tended to gain species, while slower‐rebounding lakes tended to lose species. Richness and predator presence were structured along lake area and elevation gradients, respectively. Main Conclusions Fish biodiversity of Isle Royale's lakes has remained remarkably stable over the past century, reflecting minimal anthropogenic influence. Subtle shifts suggest continuous filtering by geological and environmental processes, however, and spatial gradients in composition highlight interactions between large‐ and small‐scale filters. This study provides a valuable baseline reference for understanding the processes of community assembly and environmental change in more impacted ecosystems.

Foraminiferal and environmental change across the younger Dryas chronozone, NW Baffin Bay - Stephen J. Culver; David J. Mallinson; Seth R. Sutton; Christopher R. Moore; Allen West; Malcolm A. LeCompte (Quaternary Science Reviews, 2025)

Serum Biomarkers in Atlantic Salmon for Differential Diagnosis of Cardiomyopathy Syndrome and Pancreas Disease: Proteomic Identification of Serum Fibrinogen to Enhance Troponin Immunoassay as Optimal Diagnostic Approach - Francesca Riva; Lauren Elaine Black; Kim D. Thompson; Philippe Sourd; Andrei Bordeianu; Christopher C. Chadwick; Hooman Moghadam; Jorge Del‐Pozo; Janina Costa; Richard Burchmore; Nicola Brady; Lewis Moore; et al. (Journal of Fish Diseases, 2025)
Cardiac viral diseases are among the major causes of economic losses in Atlantic salmon ( Salmo salar L.) aquaculture. These include cardiomyopathy syndrome (CMS) caused by piscine myocarditis virus (PMCV) and pancreas disease (PD) caused by Atlantic salmonid alphavirus (SAV). The resulting cardiomyopathies impact fish stock in terms of mortality, quality, growth performance and economic loss. Diagnosis of these diseases is currently based on clinical signs, histopathology and RT‐qPCR. To identify putative biomarkers for use in the health assessment of Atlantic salmon, a quantitative proteomics investigation was undertaken with the aim of differentiating fish with CMS from healthy fish and fish with PD. Serum samples ( n = 9/group) were collected during health assessment from pens where clinical CMS or PD were present and compared to serum from healthy Atlantic salmon. There were 34 differentially abundant proteins (DAPs) in CMS compared to healthy, 66 comparing CMS to PD, and 81 comparing PD to healthy. In relation to healthy samples, most DAPs were shared between CMS and PD, with higher relative abundances observed in PD. An exception to this was serum fibrinogen, which was identified as a putative biomarker for CMS, whereas differentiation of Atlantic salmon with CMS from those with PD was enhanced by the calculation of the ratio of fibrinogen to skeletal troponin C.

Probing the mechanisms of Fe(III)/As(V) reduction and As mobilisation using mineral-coated sands; impact of electron donor treatments - Oliver C. Moore; Laura A. Richards; Christopher Boothman; Sam Shaw; Babajide Milton Macaulay; David A. Polya; Bart E. van Dongen; Jonathan R. Lloyd (Science of The Total Environment, 2025)

Ultrasound image abnormalities associated with the development of ovine pulmonary adenocarcinoma - David Collie; James Meehan; Helen Brown; Ziyuan Chang; Chris Cousens; Jo Moore; Helen Todd; David J. Griffiths; Nicole Storer; Chad E. Eckert; Mark Gray (Research in Veterinary Science, 2025)

Liming alone does not guarantee the success of sugar maple regeneration - Jean-David Moore; Rock Ouimet (Forest Ecology and Management, 2025)

Optimizing automated photo identification for population assessments - Philip T. Patton; Krishna Pacifici; Robin W. Baird; Erin M. Oleson; Jason B. Allen; Erin Ashe; Aline Athayde; Charla J. Basran; Elsa Cabrera; John Calambokidis; Júlio Cardoso; Emma L. Carroll; et al. (Conservation Biology, 2025)
Several legal acts mandate that management agencies regularly assess biological populations. For species with distinct markings, these assessments can be conducted noninvasively via capture‐recapture and photographic identification (photo‐ID), which involves processing considerable quantities of photographic data. To ease this burden, agencies increasingly rely on automated identification (ID) algorithms. Identification algorithms present agencies with an opportunity—reducing the cost of population assessments—and a challenge—propagating misidentifications into abundance estimates at a large scale. We explored several strategies for generating capture histories with an ID algorithm, evaluating trade‐offs between labor costs and estimation error in a hypothetical population assessment. To that end, we conducted a simulation study informed by 39 photo‐ID datasets representing 24 cetacean species. We fed the results into a custom optimization tool to discern the optimal strategy for each dataset. Our strategies included choosing between truly and partially automated photo‐ID and, in the case of the latter, choosing the number of suggested matches to inspect. True automation was optimal for datasets for which the algorithm identified individuals well. As identification performance declined, the optimization recommended that users inspect more suggested matches from the ID algorithm, particularly for small datasets. False negatives (i.e., individual was resighted but erroneously marked as a first capture) strongly predicted estimation error. A 2% increase in the false negative rate translated to a 5% increase in the relative bias in abundance estimates. Our framework can be used to estimate expected error of the abundance estimate, project labor effort, and find the optimal strategy for a dataset and algorithm. We recommend estimating a strategy's false negative rate before implementing the strategy in a population assessment. Our framework provides organizations with insights into the conservation benefits and consequences of automation as conservation enters a new era of artificial intelligence for population assessments.

Structural and pragmatic language skills in school-age children relate to resting state functional connectivity - Julia C. Hoyda; Hannah J. Stewart; Jennifer Vannest; Karla N. Washington; David R. Moore (Brain Imaging and Behavior, 2025)
Language difficulties are common in school-age children but their etiology is often unknown. Although neural underpinnings of language have been well-studied in neurotypical individuals, functional connectivity differences between children with language difficulties and their typically-developing peers have not. There is little evidence regarding patterns of neural connectivity for children with language difficulties. Differences in neural networks related to degree of language difficulties and subtype of language skills (structural or pragmatic) are unclear. We examined expressive and receptive language networks, and an executive function network, in school-age children (8–12 years, n = 81) relative to their caregiver-reported language skills. We hypothesized that children with poorer structural and pragmatic language skills would have decreased connectivity in these networks. Participants were separated into groups by structural and pragmatic language scores: those with structural language difficulties (SLD), pragmatic language difficulties (PLD), and combined language difficulties (CLD, consisting of some participants in both SLD and PLD). The remainder of participants were in the typical language (TL) group. Results showed trends toward increased cross-hemispheric connectivity in age-matched controls relative to those with poorer language skills. Specifically, connectivity between bilateral inferior frontal gyri and areas including bilateral supplementary motor areas, cerebellar regions, and bilateral frontal gyri was associated with higher structural and pragmatic language scores. Connectivity among additional regions including bilateral superior temporal gyri and Heschl’s gyrus showed both positive and negative correlation with both language scores. This suggests that reduced connectivity between regions involved in language processing may contribute to language difficulties in school-age children.

Limited Regulation of Canopy Water Use Efficiency by Stomatal Behavior Under Drought Propagation - Feng Li; Qinchuan Xin; Chuixiang Yi; Steven A. Kannenberg; Julia K. Green; Mirco Migliavacca; David J. P. Moore; Armen R. Kemanian; Pierre Gentine; Paul C. Stoy; Fangyue Zhang; Yujiu Xiong; et al. (Global Change Biology, 2025)
Water use efficiency (WUE) is a critical ecosystem function and a key indicator of vegetation responses to drought, yet its temporal trajectories and underlying drivers during drought propagation remain insufficiently understood. Here, we examined the trajectories, interdependencies and drivers of multidimensional WUE metrics and their components (gross primary production (GPP), evapotranspiration, transpiration (T), and canopy conductance (Gc)) using a conceptual drought propagation framework. We found that even though the carbon assimilation efficiency per stomata increases during drought, the canopy‐level WUE (represented by transpiration WUE (TWUE)) declines, indicating that stomatal regulation operates primarily at the leaf level and cannot offset the drought‐induced reduction in WUE at the canopy scale. A stronger dependence on T and TWUE indicates that the water–carbon trade‐off relationship of vegetation more inclines toward water transport than carbon assimilation. Gc fails to prevent the sharp decline in GPP during drought and has limited capacity to suppress T, as reflected by the reduction magnitude and the threshold (the turning point at which a component shifts from a normal to drought‐responsive state). The primary drivers of the water–carbon relationship under drought propagation include vapor pressure deficit and hydraulic traits. Among plant functional types, grasslands show the strongest water–carbon fluxes in response to drought, whereas evergreen broadleaf forests exhibit the weakest response. These findings refine our comprehensive understanding of multidimensional ecosystem functional dynamics under drought propagation and enlighten how the physiological response of vegetation to drought affects the carbon and water cycles.

The Seaward Migration of European Eel at a Continental Scale: A Europe‐Wide Biotelemetry Meta‐Analysis - Pieterjan Verhelst; David Righton; Kim Aarestrup; Pedro R. Almeida; Tea Bašić; Jonathan D. Bolland; Liam Carter; Johan Coeck; José Lino Costa; Justas Dainys; Jan Grimsrud Davidsen; Isabel Domingos; et al. (Fish and Fisheries, 2025)
The European eel ( Anguilla anguilla L.) has a catadromous life cycle, with a single panmictic population that colonises continental Europe and northern Africa yet migrates 5000 to 9000 km to spawn in the Atlantic Ocean. It is unknown how this continental migration is organised so individual eels arrive in time for spawning with conspecifics. This meta‐analysis combined tracking data from 18 water bodies in freshwater and transitional systems distributed along the southwest‐northeast axis of Europe, resulting in a dataset of 2306 eels, making it the most comprehensive in terms of geographical coverage and number of eels tagged. The eels were tracked using acoustic telemetry and the Nedap Trail System and allowed us to study the eel's migration phenology at a continental scale. The findings reveal that the day when eels arrive at sea varies significantly with latitude, with northern eels arriving earlier. Migration speed differs between tidal and non‐tidal habitats, suggesting that tidal currents facilitate faster movement. However, despite these patterns, we observed substantial variability in arrival at sea time and migration speed within water bodies, suggesting that the eel's migration phenology is considerably plastic. The presence of water regulating structures such as weirs, pumping stations and hydropower plants can impact migration timing and speed, potentially delaying eels, but is likely dependent on local hydrological conditions which can be water body specific.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Health and Safety in U.S. Chesapeake Bay Oyster Aquaculture: A Qualitative Study - Caitlin A. Ceryes; Elizabeth Nussbaumer; Emma E. Moynihan; E. R. H. Moore; David C. Love; Jacqueline Agnew; Roni Neff; Jillian Fry (Journal of Agromedicine, 2025)

A user’s guide to coral reef restoration terminologies - David J. Suggett; Elizabeth A. Goergen; Megan Fraser; Margaux Y. Hein; Whitney Hoot; Ian McLeod; Phanor H. Montoya-Maya; Tom Moore; Andrew M. Ross; Tali Vardi (Coral Reefs, 2025)
Global coral reef restoration efforts continue to diversify in approach, location, and socio-ecological context. In parallel, vocabulary has evolved such that practitioners, scientists, policy makers, communicators, and investors must navigate an increasingly confusing set of terms that are inconsistently defined. Precision around terms and definitions is an important attribute underpinning the rate and extent with which restoration can scale. However, in contrast with more established ecological restoration fields, coral reef restoration lacks a formal lexicon for its core approaches and processes. Here we synthesize, distill, and clarify a core lexicon proposed for coral reef restoration. We navigate readers systematically through terms used for various coral reef restoration approaches, project planning and intent, process workflows, and biological material. We also consider vague terms commonly used that present challenges to singularly define. While we expect this proposed lexicon to continue to evolve, we offer an important first step toward more integrated communications around coral reef restoration.

A numerical investigation of the effects of model parameterization on the delineation of source protection zones under uncertainty - Allanah Kenny; Theo S. Sarris; David M. Scott; Catherine Moore (Water Research, 2025)

Groundwater flowpath characteristics drive variability in per- and polyfluoroalkyl substances (PFAS) loading across a stream-wetland system - David M. Rey; Martin A. Briggs; Andrea K. Tokranov; Hayley G. Lind; Patrick T. Scordato; Ramona Darlington Iery; Henry E. Moore; Lee D. Slater; Denis R. LeBlanc (Science of The Total Environment, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Genomic Islands of Divergence Between Drosophila yakuba Subspecies are Predominantly Driven by Chromosomal Inversions and the Recombination Landscape - Erina A. Ferreira; Cathy C. Moore; David Ogereau; Arnaud Suwalski; Stéphane R. Prigent; Rebekah L. Rogers; Amir Yassin (Molecular Ecology, 2025)
During the early stages of local adaptation and speciation, genetic differences tend to accumulate at certain regions of the genome leading to the formation of genomic islands of divergence (GIDs). This pattern may be due to selection and/or difference in the rate of recombination. Here, we investigate the possible causes of GIDs in Drosophila yakuba mayottensis , and reconfirm using field collection its association with toxic noni ( Morinda citrifolia ) fruits on the Mayotte island. Population genomics revealed lack of genetic structure on the island and identified 23 GIDs distinguishing D. y. mayottensis from generalist mainland populations of D. y. yakuba . The GIDs were enriched with gene families involved in the metabolism of lipids, sugars, peptides and xenobiotics, suggesting a role in host shift. We assembled a new genome for D. y. mayottensis and identified five novel chromosomal inversions. Twenty one GIDs (~99% of outlier windows) fell in low recombining regions or subspecies‐specific inversions. However, only two GIDs were in collinear, normally recombining regions suggesting a signal of hard selective sweeps. Unlike D. y. mayottensis , D. sechellia , the only other noni‐specialist, is known to be homosequential with its generalist relatives. Thus, whereas structural variation may disproportionally shape GIDs in some species, striking parallel adaptations can occur between species despite distinct genomic architectures.

5-HT2C agonism as a neurotherapeutic for sarcopenia: preclinical proof of concept - Nathan R. Kerr; Anna R. Dashtmian; Fereshteh B. Darvishi; Charles D. Brennan; Sindhuja N. Ayyagari; Peter J. Moore; Jose A. Viteri; Meifang Wang; Mark M. Rich; Brian C. Clark; W. David Arnold (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Characterisation of dissolved organic matter in two contrasting arsenic-prone sites in Kandal Province, Cambodia - Oliver C. Moore; Amy D. Holt; Laura A. Richards; Amy M. McKenna; Robert G.M. Spencer; Dan J. Lapworth; David A. Polya; Jonathan R. Lloyd; Bart E. van Dongen (Organic Geochemistry, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Patterns in tree squirrel co-occurrence vary with responses to local land cover in US cities - Rachel N. Larson; Heather A. Sander; Mason Fidino; Julia L. Angstmann; Sheryl Hayes Hursh; Seth B. Magle; Katrina Moore; Carmen M. Salsbury; Theodore Stankowich; Katherine Tombs; Lauren Barczak; Alyssa M. Davidge; et al. (Urban Ecosystems, 2024)

Optimizing the detection of N-nitrosamine mutagenicity in the Ames test - Robert H. Heflich; Michelle E. Bishop; Roberta A. Mittelstaedt; Jian Yan; Sharon K. Guerrero; Audrey M. Sims; Kamela Mitchell; Nyosha Moore; Xilin Li; Nan Mei; Rosalie K. Elespuru; Sruthi T. King; et al. (Regulatory Toxicology and Pharmacology, 2024)

Multi-decadal aspen dynamics show recruitment bottleneck across complex mountain community - Michael T. Stoddard; Kyle C. Rodman; Connor D. Crouch; David W. Huffman; Peter Z. Fulé; Kristen M. Waring; Margaret M. Moore (Forest Ecology and Management, 2024)

Geology from aeromagnetic data - Peter G. Betts; David Moore; Alan Aitken; Teagan Blaikie; Mark Jessell; Laurent Ailleres; Robin Armit; Mark McLean; Radhakrishna Munukutla; Chibuzo Chukwu (Earth-Science Reviews, 2024)

Examining Bald Eagle Contaminant Exposure and Reproductive Risk Above and Below Dams on Great Lakes Tributaries - Carly Jasmine Eakin; Lisa Williams; Jeremy Moore; Mandy Annis; David Best; Sarah Warner; William Bowerman; Latice Fuentes; Kendall Simon; Brandon Armstrong (Archives of Environmental Contamination and Toxicology, 2024)
Removing lowermost dams can reestablish fish passage on Great Lakes tributaries. This can increase the transfer of contaminants from anadromous fish to piscivorous wildlife upstream; however, concentrations of bioaccumulative contaminants in Great Lakes fish have decreased over the last several decades. We analyzed concentrations of PCBs and the toxic equivalence (TEQs) calculated from PCBs, DDTs, other organochlorine pesticides, and PBDEs in the plasma of bald eagle nestlings above and below lowermost dams on five river systems in Michigan from 1999 to 2013. We examined relationships between contaminants and metrics of reproductive success from 1997 to 2018, including the effects of year and location relative to the lowermost dam. Σ 20 PCB and p,p’ -DDE were important in characterizing differences in contaminant mixtures above and below dams. Concentrations of contaminants were generally greater below dams than above. There were generally greater nest success and more nestlings per nest below dams, but nest location explained little variability ( R 2 values = 0.03–0.15). Neither Σ 20 PCB nor p,p’ -DDE was a significant predictor of 5-year productivity means by river reach despite concentrations exceeding previously established effects thresholds for healthy bald eagle populations in the Great Lakes (≥ 1 nestling/nest). Our study indicates that dams may continue to reduce the upstream movement of contaminants to bald eagles, but at the measured concentrations, contaminants did not impair productivity and reproductive success as indicated by nestlings per nest. Additional information about population dynamics could clarify population-level effects of contaminants on bald eagles and to what degree these populations are self-sustaining throughout the Great Lakes.

Expanded Combined Loading Injury Criterion for the Human Lumbar Spine Under Dynamic Compression - Maria Ortiz-Paparoni; Joost Op ‘t Eynde; Christopher Eckersley; Concetta Morino; Mitchell Abrams; Derek Pang; Jason Kait; Frank Pintar; Narayan Yoganandan; Jason Moore; David Barnes; Kathryn Loftis; et al. (Annals of Biomedical Engineering, 2024)

Soil solution chemistry weak response to long-term N addition points towards a strong resilience of northeastern American forests to past and future N deposition - Daniel Houle; Marie Renaudin; Louis Duchesne; Jean-David Moore; Apolline Benoist (Science of The Total Environment, 2024)

Confined within a sugarcane monoculture: A participatory assessment of water pollution and potential health risks in the community of El Tiple, Colombia - David Bahamón-Pinzón; Irene Vélez-Torres; Shanna L. Estes; Cindy Lee; Arelis Moore; William Bridges; Elizabeth Carraway; Haley Blazer; Héctor Mario Gutiérrez Zapata; Diana Vanegas (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Beneficial ‘inefficiencies’ of western ranching: Flood-irrigated hay production sustains wetland systems by mimicking historic hydrologic processes - J. Patrick Donnelly; Kelsey Jensco; John S. Kimball; Johnnie N. Moore; David Ketchum; Daniel P. Collins; David E. Naugle (Agriculture, Ecosystems & Environment, 2024)

A warming western boundary current increases the prevalence of commercially disruptive parasites in broadbill swordfish - Jessica A. Bolin; Karen Evans; David S. Schoeman; Claire M. Spillman; Thomas S. Moore; Jason R. Hartog; Scott F. Cummins; Kylie L. Scales (Fisheries Oceanography, 2024)
Meat quality is of paramount importance in the fisheries and aquaculture industries, but the quality of seafood can be affected by environmental variability and change, creating uncertainties in the delivery of consistent, high‐end product. Reports from fishers operating in an Australian fishery catching broadbill swordfish ( Xiphias gladius ) suggest that anomalously warm waters are linked with myoliquefaction of muscle tissue. The condition affects the marketability of fish by turning the meat into a soft, mushy texture post‐mortem and is caused by infection by the myxozoan parasite Kudoa musculoliquefaciens . Here, we combine microscopy, molecular techniques and ecological modelling to explore potential environmental drivers of the prevalence and intensity of K. musculoliquefaciens in swordfish, as a first step in understanding how a warming ocean might exacerbate the risk of harvesting an infected swordfish and the resultant potential risk of myoliquefaction. We develop predictive dynamic risk surfaces on seasonal timescales, with results revealing both the likelihood of harvesting an infected swordfish and the intensity of parasite load increase during the Austral summer. The prevalence of the parasite further increases in the region dominated by the East Australian Current, when locally warm areas are atypically cool and when average monthly temperatures are more variable. These findings provide information useful in predicting the conditions under which the risk of harvesting infected swordfish might be intensified, enabling adaptation to climate change impacts and optimisation of decision‐making when fishing under risky conditions.

Alzheimer-Type Cerebral Amyloidosis in the Context of HIV Infection: Implications for a Proposed New Treatment Approach - Ronald J. Ellis; Shibangi Pal; Cristian L. Achim; Erin Sundermann; David J. Moore; Virawudh Soontornniyomkij; Howard Feldman (Journal of Neuroimmune Pharmacology, 2024)
Reverse transcriptase inhibitors (RTIs) are currently broadly prescribed for the treatment of HIV infection but are also thought to prevent Alzheimer’s disease (AD) progression by protecting against amyloidosis. Our study evaluates the hypothesis that reverse transcriptase inhibitors protect against Alzheimer-type brain amyloidogenesis in the context of HIV infection. We compiled a case series of participants from a prospective study of the neurological consequences of HIV infection at the HIV Neurobehavioral Research Program (HNRP) who had serial neuropsychological and neurological assessments and were on RTIs. Two participants had gross and microscopic examination and immunohistochemistry of the brain at autopsy; one was assessed clinically for Alzheimer’s disease by cerebrospinal fluid (CSF) analysis of phosphorylated-Tau, Total-Tau and Aβ42. Additionally, a larger cohort of 250 autopsied individuals was evaluated for presence of amyloid plaques, Tau, and related pathologies. Three older, virally suppressed individuals with HIV who had long-term treatment with RTIs were included in analyses. Two cases demonstrated substantial cerebral amyloid deposition at autopsy. The third case met clinical criteria for AD based on a typical clinical course and CSF biomarker profile. In the larger cohort of autopsied individuals, the prevalence of cerebral amyloidosis among people with HIV (PWH) was greater for those on RTIs. Our study showed that long-term RTI therapy did not protect against Alzheimer-type brain amyloidogenesis in the context of HIV infection in these patients. Given the known toxicities of RTIs, it is premature to recommend them to individuals at risk or with Alzheimer’s disease who do not have HIV infection.

Seismic monitoring of EGS fracture stimulations at Utah FORGE (Part 1): Time-lapse variations of b-values and Shear-wave Splitting Rates of induced microearthquakes - David Li; Lianjie Huang; Yingping Li; Yingcai Zheng; Joseph Moore (Geothermics, 2024)

Feeding Ration Impacts Larval Pimephales Promelas 7-Day Subchronic Growth Endpoint: Case Study with Perfluorooctanesulfonic Acid - Jonna Boyda; David Moore; Paige Krupa; Ashley Kimble; Thomas Biber; Lauren May; Alan Kennedy (Archives of Environmental Contamination and Toxicology, 2024)
The larval fathead minnow, Pimephales promelas , 7-day subchronic survival and growth standard toxicity test method is commonly used for research and regulatory testing of effluents and compounds, including emerging contaminants such as Perfluorooctanesulfonic Acid (PFOS). Existing feeding guidelines for testing are described in multiple methods but are open to interpretation. The current study sought to determine the impact of feeding ration on P. promelas survival and biomass during a subchronic exposure to PFOS. The study was conducted in two phases: (1) a control experiment to determine the most significant feeding ration factors that maximize biomass, with consideration to laboratory logistics, and (2) application of down-selected feeding rations in a PFOS exposure to determine toxicity reference values. The control optimization study supported that feeding ration and feeding frequency were significant factors in fish biomass. In the subsequent PFOS study, fish were fed a high or low ration of Artemia twice daily, while exposed to 0.3 to 3.4 mg/L PFOS. Fish fed a high ration of Artemia had significantly ( p p 50 = 2.44 mg/L; low ration LC 50 = 2.25 mg/L). These findings contribute to a better understanding of the impact feeding ration has in toxicity assessments and downstream regulatory decisions.

Upscaling marine forest restoration: challenges, solutions and recommendations from the Green Gravel Action Group - Georgina Valentine Wood; Karen Filbee-Dexter; Melinda Ann Coleman; Jurgen Valckenaere; J. David Aguirre; Paige M. Bentley; Paul Carnell; Phoebe Damayanthi Dawkins; Lauren N. Dykman; Hannah S. Earp; Leeann B. Ennis; Prue Francis; et al. (Frontiers in Marine Science, 2024)
Introduction To counteract the rapid loss of marine forests globally and meet international commitments of the UN Decade on Ecosystem Restoration and the Convention on Biological Diversity ‘30 by 30’ targets, there is an urgent need to enhance our capacity for macroalgal restoration. The Green Gravel Action Group (GGAG) is a global network of 67 members that are working on the restoration of a diverse range of macroalgal forests and it aims to facilitate knowledge exchange to fast-track innovation and implementation of outplanting approaches worldwide. Methods Here, we overview 25 projects conducted by members of the group that are focused on testing and developing techniques for macroalgal restoration. Based on these projects, we summarise the major challenges associated with scaling up the area of marine forests restored. Results We identify several critical challenges that currently impede more widespread rollout of effective large-scale macroalgal restoration worldwide: 1) funding and capacity limitations, 2) difficulties arising from conditions at restoration sites, 3) technical barriers, and 4) challenges at the restoration-policy interface. Discussion Despite these challenges, there has been substantial progress, with an increasing number of efforts, community engagement and momentum towards scaling up activities in recent years. Drawing on the collective expertise of the GGAG, we outline key recommendations for the scaling up of restoration efforts to match the goals of international commitments. These include the establishment of novel pathways to fund macroalgal restoration activities, building skills and capacity, harnessing emerging innovations in mobile hatchery and seeding technologies, and the development of the scientific and governance frameworks necessary to implement and monitor macroalgal restoration projects at scale.

Identification of Regulatory Elements in Primary Sensory Neurons Involved in Trauma-Induced Neuropathic Pain - Kimberly E. Stephens; Cedric Moore; David A. Vinson; Bryan E. White; Zachary Renfro; Weiqiang Zhou; Zhicheng Ji; Hongkai Ji; Heng Zhu; Yun Guan; Sean D. Taverna (Molecular Neurobiology, 2024)
Chronic pain is a significant public health issue that is often refractory to existing therapies. Here we use a multiomic approach to identify cis-regulatory elements that show differential chromatin accessibility and reveal transcription factor (TF) binding motifs with functional regulation in the rat dorsal root ganglion (DRG), which contain cell bodies of primary sensory neurons, after nerve injury. We integrated RNA-seq to understand how differential chromatin accessibility after nerve injury may influence gene expression. Using TF protein arrays and chromatin immunoprecipitation-qPCR, we confirmed C/EBPγ binding to a differentially accessible sequence and used RNA-seq to identify processes in which C/EBPγ plays an important role. Our findings offer insights into TF motifs that are associated with chronic pain. These data show how interactions between chromatin landscapes and TF expression patterns may work together to determine gene expression programs in rat DRG neurons after nerve injury.

Short-Term Recovery of Pilot Living Shoreline Projects for Salt Marsh Habitat in New Hampshire - James Grant McKown; Gregg E. Moore; David M. Burdick; Thomas P. Ballestero; Natalie A. White (Estuaries and Coasts, 2024)

Constraints from lamprophyre petrogenesis on the timing of Eocene lithospheric thinning and associated rifting of Borneo and Sulawesi - David Murphy; Tim A. Moore; D. Hendra Amijaya; Ferian Anggara; Mike Friederich; Carmen Gaina; Jessica Trofimovs; Hayden Dalton; Edafe Ominigbo (Journal of Asian Earth Sciences, 2024)

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Megafire: An ambiguous and emotive term best avoided by science - Cathelijne R. Stoof; Jasper R. de Vries; Marc Castellnou Ribau; Mariña F. Fernández; David Flores; Julissa Galarza Villamar; Nicholas Kettridge; Desmond Lartey; Peter F. Moore; Fiona Newman Thacker; Susan J. Prichard; Pepijn Tersmette; et al. (Global Ecology and Biogeography, 2024)
Background As fire regimes are changing and wildfire disasters are becoming more frequent, the term megafire is increasingly used to describe impactful wildfires, under multiple meanings, both in academia and popular media. This has resulted in a highly ambiguous concept. Approach We analysed the use of the term ‘megafire’ in popular media to determine its origin, its developments over time, and its meaning in the public sphere. We subsequently discuss how relative the term ‘mega’ is, and put this in the context of an analysis of Portuguese and global data on fire size distribution. Results We found that ‘megafire’ originated in the popular news media over 20 years before it appeared in science. Megafire is used in a diversity of languages, considers landscape fires as well as urban fires, and has a variety of meanings in addition to size. What constitutes ‘mega’ is relative and highly context‐dependent in space and time, given variation in landscape, climate, and anthropogenic controls, and as revealed in examples from the Netherlands, Portugal and the Global Fire Atlas. Moreover, fire size does not equate to fire impact. Conclusion Given the diverse meanings of megafire in the popular media, we argue that redefining megafire in science potentially leads to greater disparity between science and practice. Megafire is widely used as an emotive term that is best left for popular media. For those wanting to use it in science, what constitutes a megafire should be defined by the context in which it is used, not by a metric of one‐size‐fits‐all.

The energy content of meals with a similar macronutrient distribution may have a greater impact on appetite sensations than food preferences in adolescents with obesity: A secondary analysis - Halim Moore; Julie Siroux; Bruno Pereira; Maud Miguet; Alicia Fillon; Celine Dionnet; Valérie Julian; Martine Duclos; Yves Boirie; Graham Finlayson; Laurie Isacco; David Thivel (Appetite, 2023)

The use of Beauveria bassiana for the control of the larger grain borer, Prostephanus truncatus, in stored maize: Semi-field trials in Ghana - Belinda Luke; Mavis A. Acheampong; Drauzio E.N. Rangel; Eric W. Cornelius; Stephen K. Asante; Jerry A. Nboyine; Vincent Y. Eziah; Ken O. Fening; Clare Storm; Nick Jessop; Victor A. Clottey; Olivier Potin; et al. (Fungal Biology, 2023)

The relationship between synaptodendritic neuropathology and HIV-associated neurocognitive disorders is moderated by cognitive reserve - Arin Fisher; David J. Moore; Andrew J. Levine; Eliezer Masliah; Ben Gouaux; Virawudh Soontornniyomkij; Scott Letendre; Erin E. Sundermann (Journal of NeuroVirology, 2023)

Improved net carbon budgets in the US Midwest through direct measured impacts of enhanced weathering - Ilsa B. Kantola; Elena Blanc‐Betes; Michael D. Masters; Elliot Chang; Alison Marklein; Caitlin E. Moore; Adam von Haden; Carl J. Bernacchi; Adam Wolf; Dimitar Z. Epihov; David J. Beerling; Evan H. DeLucia (Global Change Biology, 2023)
Terrestrial enhanced weathering (EW) through the application of Mg‐ or Ca‐rich rock dust to soil is a negative emission technology with the potential to address impacts of climate change. The effectiveness of EW was tested over 4 years by spreading ground basalt (50 t ha −1 year −1 ) on maize/soybean and miscanthus cropping systems in the Midwest US. The major elements of the carbon budget were quantified through measurements of eddy covariance, soil carbon flux, and biomass. The movement of Mg and Ca to deep soil, released by weathering, balanced by a corresponding alkalinity flux, was used to measure the drawdown of CO 2 , where the release of cations from basalt was measured as the ratio of rare earth elements to base cations in the applied rock dust and in the surface soil. Basalt application stimulated peak biomass and net primary production in both cropping systems and caused a small but significant stimulation of soil respiration. Net ecosystem carbon balance (NECB) was strongly negative for maize/soybean (−199 to −453 g C m −2 year −1 ) indicating this system was losing carbon to the atmosphere. Average EW (102 g C m −2 year −1 ) offset carbon loss in the maize/soybean by 23%–42%. NECB of miscanthus was positive (63–129 g C m −2 year −1 ), indicating carbon gain in the system, and EW greatly increased inorganic carbon storage by an additional 234 g C m −2 year −1 . Our analysis indicates a co‐deployment of a perennial biofuel crop (miscanthus) with EW leads to major wins—increased harvested yields of 29%–42% with additional carbon dioxide removal (CDR) of 8.6 t CO 2 ha −1 year −1 . EW applied to maize/soybean drives a CDR of 3.7 t CO 2 ha −1 year −1 , which partially offsets well‐established carbon losses from soil from this crop rotation. EW applied in the US Midwest creates measurable improvements to the carbon budgets perennial bioenergy crops and conventional row crops.

Mercury in Neotropical birds: a synthesis and prospectus on 13 years of exposure data - Christopher J. Sayers; David C. Evers; Viviana Ruiz-Gutierrez; Evan Adams; Claudia M. Vega; Jessica N. Pisconte; Vania Tejeda; Kevin Regan; Oksana P. Lane; Abidas A. Ash; Reynold Cal; Stevan Reneau; et al. (Ecotoxicology, 2023)
Environmental mercury (Hg) contamination of the global tropics outpaces our understanding of its consequences for biodiversity. Knowledge gaps of pollution exposure could obscure conservation threats in the Neotropics: a region that supports over half of the world’s species, but faces ongoing land-use change and Hg emission via artisanal and small-scale gold mining (ASGM). Due to their global distribution and sensitivity to pollution, birds provide a valuable opportunity as bioindicators to assess how accelerating Hg emissions impact an ecosystem’s ability to support biodiversity, and ultimately, global health. We present the largest database on Neotropical bird Hg concentrations ( n = 2316) and establish exposure baselines for 322 bird species spanning nine countries across Central America, South America, and the West Indies. Patterns of avian Hg exposure in the Neotropics broadly align with those in temperate regions: consistent bioaccumulation across functional groups and high spatiotemporal variation. Bird species occupying higher trophic positions and aquatic habitats exhibited elevated Hg concentrations that have been previously associated with reductions in reproductive success. Notably, bird Hg concentrations were over four times higher at sites impacted by ASGM activities and differed by season for certain trophic niches. We developed this synthesis via a collaborative research network, the Tropical Research for Avian Conservation and Ecotoxicology (TRACE) Initiative, which exemplifies inclusive, equitable, and international data-sharing. While our findings signal an urgent need to assess sampling biases, mechanisms, and consequences of Hg exposure to tropical avian communities, the TRACE Initiative provides a meaningful framework to achieve such goals. Ultimately, our collective efforts support and inform local, scientific, and government entities, including Parties of the United Nations Minamata Convention on Mercury, as we continue working together to understand how Hg pollution impacts biodiversity conservation, ecosystem function, and public health in the tropics.

Combined effects of loneliness and inflammation on depression in people with HIV - Mariam A. Hussain; C. Wei-Ming Watson; Erin E. Morgan; Robert K. Heaton; Scott L. Letendre; Dilip V. Jeste; David J. Moore; Jennifer E. Iudicello (Journal of NeuroVirology, 2023)
Objective Loneliness is prevalent in people with HIV (PWH) and associated with adverse health-related consequences, including depression. Chronic inflammation has been linked to depression in PWH, though its association with loneliness is less well established. Simultaneous examination of inflammation, loneliness and depression is needed to clarify these relationships. This study investigated the relationship between loneliness and inflammation, and the effects of loneliness and inflammation on depression in PWH. Methods 82 PWH who were on suppressive ART (mean age [SD] = 53.2 [9.0]) completed the UCLA Loneliness Scale-Version 3 and the Center for Epidemiologic Studies Depression Scale as part of a comprehensive evaluation. Biomarkers of systemic inflammation (CRP, IL-6, CCL2/MCP-1, sCD14) and coagulation (D-dimer) were measured in blood using commercial immunoassays. Results Multivariable linear regression analyses revealed that higher D-dimer, CCL2/MCP-1, and sCD14 were significant predictors of loneliness ( p s < .05) while accounting for relevant covariates. Stepwise multiple linear regression models that included loneliness, biomarkers, and their interactions as predictors of depressive symptoms revealed significant main effects of loneliness and CCL2/MCP-1 levels ( p s < .05), and a significant loneliness by D-dimer interaction ( p < .05) whereby higher D-dimer was associated with increased depressive symptoms only at higher levels of loneliness. Conclusions Increased coagulation activity is associated with loneliness, and in the context of loneliness, may increase risk for depression. Increased inflammation was associated with depression suggesting potentially dissociable underlying biological processes. To the extent that these processes are modifiable, such findings could have important implications in the treatment of loneliness and depression in PWH.

OME-Zarr: a cloud-optimized bioimaging file format with international community support - Josh Moore; Daniela Basurto-Lozada; Sébastien Besson; John Bogovic; Jordão Bragantini; Eva M. Brown; Jean-Marie Burel; Xavier Casas Moreno; Gustavo de Medeiros; Erin E. Diel; David Gault; Satrajit S. Ghosh; et al. (Histochemistry and Cell Biology, 2023)
A growing community is constructing a next-generation file format (NGFF) for bioimaging to overcome problems of scalability and heterogeneity. Organized by the Open Microscopy Environment (OME), individuals and institutes across diverse modalities facing these problems have designed a format specification process (OME-NGFF) to address these needs. This paper brings together a wide range of those community members to describe the cloud-optimized format itself—OME-Zarr—along with tools and data resources available today to increase FAIR access and remove barriers in the scientific process. The current momentum offers an opportunity to unify a key component of the bioimaging domain—the file format that underlies so many personal, institutional, and global data management and analysis tasks.

Warming waters of the Gulf of Maine: The role of Shelf, Slope and Gulf Stream Water masses - David W. Townsend; Neal R. Pettigrew; Maura A. Thomas; Stephen Moore (Progress in Oceanography, 2023)

IMI ConcePTION core data elements for pregnancy pharmacovigilance studies using primary source data collection methods - Jonathan Richardson; Alan Moore; Rebecca Bromley; Michael Stellfeld; Yvonne Geissbühler; Matthew Bluett-Duncan; Ursula Winterfeld; Guillaume Favre; Kenneth Hodson; Alison Oliver; Amalia Alexe; Yrea van Rijt-Weetink; et al. (Neurotoxicology and Teratology, 2023)

Verification and benchmarking relativistic electron beam transport through a background gas - Brandon M. Medina; Pierre Grua; Keith L. Cartwright; David Hébert; Nicolas Szalek; Clément Caizergues; Israel Owens; Elaine L. Rhoades; Jacques Gardelle; Christopher H. Moore (Computer Physics Communications, 2023)

Revisiting the mutagenicity and genotoxicity of N-nitroso propranolol in bacterial and human in vitro assays - Xilin Li; Yuan Le; Ji-Eun Seo; Xiaoqing Guo; Yuxi Li; Si Chen; Roberta A. Mittelstaedt; Nyosha Moore; Sharon Guerrero; Audrey Sims; Sruthi T. King; Aisar H. Atrakchi; et al. (Regulatory Toxicology and Pharmacology, 2023)

TAAR1 Regulates Purinergic-induced TNF Secretion from Peripheral, But Not CNS-resident, Macrophages - David A. Barnes; Marius C. Hoener; Craig S. Moore; Mark D. Berry (Journal of Neuroimmune Pharmacology, 2023)

Growing and non-growing season nitrous oxide emissions from a manured semiarid cropland soil under irrigation - Robert S. Dungan; April B. Leytem; Amber D. Moore; David L. Bjorneberg; Peter R. Grace; Christian Brunk; David W. Rowlings (Agriculture, Ecosystems & Environment, 2023)

Chemistry of soil and foliage in declining sugar maple stands over 13 years of nitrogen addition - Jean-David Moore; Daniel Houle (Forest Ecology and Management, 2023)

Evaluating Thin-Layer Sediment Placement as a Tool for Enhancing Tidal Marsh Resilience: a Coordinated Experiment Across Eight US National Estuarine Research Reserves - Kenneth B. Raposa; Andrea Woolfolk; Charlie A. Endris; Monique C. Fountain; Gregg Moore; Megan Tyrrell; Rebecca Swerida; Scott Lerberg; Brandon J. Puckett; Matthew C. Ferner; Jeffrey Hollister; David M. Burdick; et al. (Estuaries and Coasts, 2023)

Eddy and tidal driven basal melting of the Totten and Moscow University ice shelves - Yuwei Xia; David E. Gwyther; Ben Galton-Fenzi; Eva A. Cougnon; Alexander D. Fraser; John C. Moore (Frontiers in Marine Science, 2023)
The mass loss from the neighboring Totten and Moscow University ice shelves is accelerating and may raise global sea levels in coming centuries. Totten Glacier is mostly based on bedrock below sea level, and so is vulnerable to warm water intrusion reducing its ice shelf buttressing. The mechanisms driving the ocean forced sub-ice-shelf melting remains to be further explored. In this study, we simulate oceanic-driven ice shelf melting of the Totten (TIS) and Moscow University ice shelves (MUIS) using a high spatiotemporal resolution model that resolves both eddy and tidal processes. We selected the year 2014 as representative of the period 1992 to 2017 to investigate how basal melting varies on spatial and temporal scales. We apply the wavelet coherence method to investigate the interactions between the two ice shelves in time-frequency space and hence estimate the contributions from tidal (<1.5 days) and eddy (2-35 days) components of the ocean heat transport to the basal melting of each ice shelf. In our simulation, the 2014 mean basal melt rate for TIS is 6.7 m yr -1 (42 Gt yr -1 ) and 9.7 m yr -1 (52 Gt yr -1 ) for MUIS. We find high wavelet coherence in the eddy dominated frequency band between the two ice shelves over almost the whole year. The wavelet coherence along five transects across the ice shelves suggests that TIS basal melting is dominated by eddy processes, while MUIS basal melting is dominated by tidal processes. The eddy-dominated basal melt for TIS is probably due to the large and convoluted bathymetric gradients beneath the ice shelf, weakening higher frequency tidal mode transport. This illustrates the key role of accurate bathymetric data plays in simulating on-going and future evolution of these important ice shelves.

Runnels Reverse Mega-pool Expansion and Improve Marsh Resiliency in the Great Marsh, Massachusetts (USA) - J. Grant McKown; David M. Burdick; Gregg E. Moore; Christopher R. Peter; Andrew R. Payne; Jennifer L. Gibson (Wetlands, 2023)

HBM4EU feasibility studies: Lessons learned in combining health and human biomonitoring studies - Hanna Maria Elonheimo; Karoliina Uusitalo; Sonja Moore; Anna-Maria Andersson; Ronny Baber; Kerstin Wirkner; Madlen David; Marike Kolossa-Gehring; Lorraine Stewart; Ovnair Sepai; Dominik Lermen; Martina Bartel-Steinbach; et al. (International Journal of Hygiene and Environmental Health, 2023)

The role of electron donors in arsenic-release by redox-transformation of iron oxide minerals – A review - Oliver C. Moore; Wei Xiu; Huaming Guo; David A. Polya; Bart E. van Dongen; Jonathan R. Lloyd (Chemical Geology, 2023)

Living on the edge: thermal limitations of zebra mussels (Dreissena polymorpha) in Central Texas - Astrid N. Schwalb; David Swearingen; Josi J. Robertson; Jason L. Locklin; Josiah S. Moore; Monica McGarrity (Biological Invasions, 2023)

Physiological response of mature red spruce trees to partial and complete sapwood severing - Kelly L. French; Matthew A. Vadeboncoeur; Heidi Asbjornsen; Laura S. Kenefic; David B. Moore; Jay W. Wason (Theoretical and Experimental Plant Physiology, 2023)

Allometric scaling exponents for individual amino acids differ significantly from that of protein in juvenile barramundi (Lates calcarifer). - David Poppi; Michael Salini; Stephen Moore; Cedric Simon; Brett Glencross (Aquaculture, 2023)

The rank abundance distribution of large-bodied vertebrates from Natural Trap Cave, Wyoming - Cory M. Redman; Jason R. Moore; David M. Lovelace; Julie A. Meachen (Quaternary International, 2023)

The National Conference on Health Disparities Student Research Forum - Marvella E. Ford; Angela M. Malek; Erica Martino; Latecia Abraham-Hilaire; Oluwole Ariyo; Dana Burshell; Gloria Callwood; Laura Campbell; Kimberly Cannady; Courtney Chavis; Brittney Crawford; Andie Edwards; et al. (Journal of Cancer Education, 2023)
The annual National Conference on Health Disparities (NCHD) was launched in 2000. It unites health professionals, researchers, community leaders, and government officials, and is a catalyzing force in developing policies, research interventions, and programs that address prevention, social determinants, health disparities, and health equity. The NCHD Student Research Forum (SRF) was established in 2011 at the Medical University of South Carolina to build high-quality biomedical research presentation capacity in primarily underrepresented undergraduate and graduate/professional students. This paper describes the unique research training and professional development aspects of the NCHD SRF. These include guidance in abstract development, a webinar on presentation techniques and methods, a vibrant student-centric conference, and professional development workshops on finding a mentor and locating scholarship/fellowship funding, networking, and strategies for handling ethical issues in research with mentors. Between 2011 and 2018, 400 undergraduate and graduate/professional students participated in the NCHD SRF. Most students were women (80.5%). Approximately half were African American or black (52.3%), 18.0% were white, and 21.3% were of Hispanic/Latinx ethnicity. The NCHD SRF is unique in several ways. First, it provides detailed instructions on developing a scientific abstract, including content area examples. Second, it establishes a mandatory pre-conference training webinar demonstrating how to prepare a scientific poster. Third, it works with the research mentors, faculty advisors, department chairs, and deans to help identify potential sources of travel funding for students with accepted abstracts. These features make the NCHD SRF different from many other conferences focused on students’ scientific presentations.

Development and Validation of a Western Blot Method to Quantify Mini-Dystrophin in Human Skeletal Muscle Biopsies - Catherine I. Soderstrom; Jennifer Larsen; Carolina Owen; David Gifondorwa; David Beidler; Florence H. Yong; Patricia Conrad; Hendrik Neubert; Steven A. Moore; Mohamed Hassanein (The AAPS Journal, 2022)
Duchenne muscular dystrophy (DMD) is a degenerative muscular disease affecting roughly one in 5000 males at birth. The disease is often caused by inherited X-linked recessive pathogenic variants in the dystrophin gene, but may also arise from de novo mutations. Disease-causing variants include nonsense, out of frame deletions or duplications that result in loss of dystrophin protein expression. There is currently no cure for DMD and the few treatment options available aim at slowing muscle degradation. New advances in gene therapy and understanding of dystrophin (DYS) expression in other muscular dystrophies have opened new opportunities for treatment. Therefore, reliable methods are needed to monitor dystrophin expression and assess the efficacy of new therapies for muscular dystrophies such as DMD and Becker muscular dystrophy (BMD). Here, we describe the validation of a novel Western blot (WB) method for the quantitation of mini-dystrophin protein in human skeletal muscle tissues that is easy to adopt in most laboratory settings. This WB method was assessed through precision, accuracy, selectivity, dilution linearity, stability, and repeatability. Based on mini-DYS standard performance, the assay has a dynamic range of 0.5–15 ng protein (per 5 µg total protein per lane), precision of 3.3 to 25.5%, and accuracy of − 7.5 to 3.3%. Our stability assessment showed that the protein is stable after 4 F/T cycles, up to 2 h at RT and after 7 months at − 70°C. Furthermore, our WB method was compared to the results from our recently published LC–MS method. Graphical Abstract Workflow for our quantitative WB method to determine mini-dystrophin levels in muscle tissues (created in Biorender.com). Step 1 involves protein extraction from skeletal muscle tissue lysates from control, DMD, or BMD biospecimen. Step 2 measures total protein concentrations. Step 3 involves running gel electrophoresis with wild-type dystrophin (wt-DYS) from muscle tissue extracts alongside mini-dystrophin STD curve and mini-DYS and protein normalization with housekeeping GAPDH.

Amplifying actions for food system transformation: insights from the Stockholm region - David P. M. Lam; Amanda Jiménez-Aceituno; Leonie Guerrero Lara; My M. Sellberg; Albert V. Norström; Michele-Lee Moore; Garry D. Peterson; Per Olsson (Sustainability Science, 2022)
Food is essential to people and is one of the main ways in which people are connected to the world’s ecosystems. However, food systems often cause ecosystem degradation and produce ill-health, which has generated increasing calls to transform food systems to be more sustainable. The Swedish food system is currently undergoing substantial change. A varied set of local actors have created alternative sustainability initiatives that enact new ways of doing, thinking, and organizing. These actors can increase the transformative impact of their initiatives through multiple actions and a variety of amplification processes. We analyzed the actions adopted by 29 food initiatives active in the Stockholm region using information available online. We conducted 11 interviews to better understand the amplification processes of speeding up (i.e., accelerating impact) , scaling up (i.e., influencing higher institutional levels), and scaling deep (i.e., changing values and mind-sets). Our results indicated that the initiatives mainly seek to stabilize and grow their impact while changing the awareness, values, and mind-sets of people concerning the food they consume ( scaling deep ). However, these approaches raise new questions about whether these actions subvert or reinforce current unsustainable and inequitable system dynamics. We suggest there are distinct steps that local and regional governments could take to support these local actors via collaborations with coordinated forms of initiatives, and fostering changes at the municipality level, but these steps require ongoing, adaptive approaches given the highly complex nature of transformative change and the risks of reinforcing current system dynamics.

The policy and ecology of forest-based climate mitigation: challenges, needs, and opportunities - Courtney L. Giebink; Grant M. Domke; Rosie A. Fisher; Kelly A. Heilman; David J. P. Moore; R. Justin DeRose; Margaret E. K. Evans (Plant and Soil, 2022)

Hormetic association between perceived stress and human epigenetic aging based on resilience capacity - Sharon H. Bergquist; Danyang Wang; Alicia K. Smith; David L. Roberts; Miranda A. Moore (Biogerontology, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Acute tryptophan depletion alters affective touch perception - Paula D. Trotter; Sharon A. Smith; David J. Moore; Noreen O’Sullivan; Martyn M. McFarquhar; Francis P. McGlone; Susannah C. Walker (Psychopharmacology, 2022)
Rationale Affiliative tactile interactions help regulate physiological arousal and confer resilience to acute and chronic stress. C-tactile afferents (CTs) are a population of unmyelinated, low threshold mechanosensitive cutaneous nerve fibres which respond optimally to a low force stimulus, moving at between 1 and 10 cm/s. As CT firing frequencies correlate positively with subjective ratings of touch pleasantness, they are hypothesised to form the first stage of encoding affiliative tactile interactions. Serotonin is a key modulator of social responses with known effects on bonding. Objectives The aim of the present study was to determine the effect of acutely lowering central serotonin levels on perceptions of CT-targeted affective touch. Methods In a double blind, placebo-controlled design, the effect of acute tryptophan depletion (ATD) on 25 female participants’ ratings of directly and vicariously experienced touch was investigated. Psychophysical techniques were used to deliver dynamic tactile stimuli; some velocities were targeted to optimally activate CTs (1–10 cm/s), whereas other, faster and slower strokes fell outside the CT optimal range. Discriminative tactile function, cold pain threshold and tolerance were also measured. Results ATD significantly increased pleasantness ratings of both directly and vicariously experienced affective touch, increasing discrimination of the specific hedonic value of CT targeted velocities. While ATD had no effect on either tactile or cold pain thresholds, there was a trend for reduced tolerance to cold pain. Conclusions These findings are consistent with previous reports that depletion of central serotonin levels modulates neural and behavioural responsiveness to appetitive sensory signals.

Length of growing season is modulated by Northern Hemisphere jet stream variability - Amy R. Hudson; William K. Smith; David J. P. Moore; Valerie Trouet (International Journal of Climatology, 2022)
Atmospheric circulations create regions of similar climate at the land surface across the Northern Hemisphere's mid‐latitudes, while climate controls on plant phenology phases (phenophases) can vary. Here, we quantify and classify the seasonal impacts of the Northern Hemisphere jet stream (NHJ) on vegetation phenophases using novel NHJ indices, designed to characterize latitudinal jet stream position, and satellite‐based vegetation phenology products of length, start, and end of season (LOS, SOS, EOS). We composited years of northern and southern NHJ anomalies in April–May and October–November from LOS, SOS, and EOS and classified ecosystem response based on: latitudinal location relative to the climatological mean (CM) latitude of the NHJ; climate; and land cover type. For nearly a third of the NH, LOS was modulated by NHJ position. The magnitude and direction of NHJ influence on LOS was dependent on the season of NHJ position anomaly. In spring, a northern NHJ, which typically corresponded with warmer temperatures, led to earlier SOS and longer LOS, especially in cold systems north of the NHJ's CM. Surprisingly, in fall, a northern NHJ led to shorter LOS and earlier EOS for most systems, which may be due to the interaction of temperature and water availability in this season when water is critical for sustained growth. Southern NHJ corresponded with similar but opposite effects on phenophases. Crop land cover was mixed in LOS response to NHJ, reflecting the added impact of land‐use and management. The NHJ can synchronize phenology across apparently disparate regions of the Northern Hemisphere. Rather than simply lengthening or shortening seasons as the NHJ moves northward or southward, the influence of the NHJ on phenology at a given location depends on whether the NHJ is limiting resources—which vary relative to the climatological mean. We find that complex patterns in phenology emerge from a relatively simple contingency.

Global increase in methane production under future warming of lake bottom waters - Joachim Jansen; Richard Iestyn Woolway; Benjamin M. Kraemer; Clément Albergel; David Bastviken; Gesa A. Weyhenmeyer; Rafael Marcé; Sapna Sharma; Sebastian Sobek; Lars J. Tranvik; Marjorie Perroud; Malgorzata Golub; et al. (Global Change Biology, 2022)
Lakes are significant emitters of methane to the atmosphere, and thus are important components of the global methane budget. Methane is typically produced in lake sediments, with the rate of methane production being strongly temperature dependent. Local and regional studies highlight the risk of increasing methane production under future climate change, but a global estimate is not currently available. Here, we project changes in global lake bottom temperatures and sediment methane production rates from 1901 to 2099. By the end of the 21st century, lake bottom temperatures are projected to increase globally, by an average of 0.86–2.60°C under Representative Concentration Pathways (RCPs) 2.6–8.5, with greater warming projected at lower latitudes. This future warming of bottom waters will likely result in an increase in methane production rates of 13%–40% by the end of the century, with many low‐latitude lakes experiencing an increase of up to 17 times the historical (1970–1999) global average under RCP 8.5. The projected increase in methane production will likely lead to higher emissions from lakes, although the exact magnitude of the emission increase requires more detailed regional studies.

Influence of Rising Water Temperature on the Temperate Seagrass Species Eelgrass (Zostera marina L.) in the Northeast USA - Holly K. Plaisted; Erin C. Shields; Alyssa B. Novak; Christopher P. Peck; Forest Schenck; Jillian Carr; Paul A. Duffy; N. Tay Evans; Sophia E. Fox; Stephen M. Heck; Robbie Hudson; Trevor Mattera; et al. (Frontiers in Marine Science, 2022)
Sea surface temperature (SST) has increased worldwide since the beginning of the 20th century, a trend which is expected to continue. Changes in SST can have significant impacts on marine biota, including population-level shifts and alterations in community structure and diversity, and changes in the timing of ecosystem events. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems, where they provide many ecosystem services. Eelgrass, Zostera marina L., is the dominant seagrass species in the Northeast United States of America (USA). Multiple factors have been cited for losses in this region, including light reduction, eutrophication, and physical disturbance. Warming has the potential to exacerbate seagrass loss. Here, we investigate regional changes in eelgrass presence and abundance in relation to local water temperature using monitoring data from eight sites in the Northeastern USA (New Hampshire to Maryland) where a consistent monitoring protocol, SeagrassNet, has been applied. We use a hurdle model consisting of a generalized additive mixed model (GAMM) with binomial and beta response distributions for modeling eelgrass presence and abundance, respectively, in relation to the local summer average water temperature. We show that summer water temperature one year prior to monitoring is a significant predictor of eelgrass presence, but not abundance, on a regional scale. Above average summer temperatures correspond to a decrease in probability of eelgrass presence (and increased probability of eelgrass absence) the following year. Cooler than average temperatures in the preceding year, down to approximately 0.5°C below the site average, are associated with the highest predicted probability of eelgrass presence. Our findings suggest vulnerability in eelgrass meadows of the Northeast USA and emphasize the value of unified approaches to seagrass monitoring, conservation and management at the seascape scale.

Tissue Distribution of Mercury in the Bodies of Wild American Alligators (Alligator mississippiensis) from a Coastal Marsh in Louisiana (USA) - Liberty A. Moore; John W. Finger; David L. Haskins; Ruth M. Elsey; Steven B. Castleberry; Travis C. Glenn; Charles H. Jagoe; I. Lehr Brisbin (Archives of Environmental Contamination and Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Long-term Annual Aerial Surveys of Submersed Aquatic Vegetation (SAV) Support Science, Management, and Restoration - Robert J. Orth; William C. Dennison; Cassie Gurbisz; Michael Hannam; Jeni Keisman; J. Brooke Landry; Jonathan S. Lefcheck; Kenneth A. Moore; Rebecca R. Murphy; Christopher J. Patrick; Jeremy Testa; Donald E. Weller; et al. (Estuaries and Coasts, 2022)
Aerial surveys of coastal habitats can uniquely inform the science and management of shallow, coastal zones, and when repeated annually, they reveal changes that are otherwise difficult to assess from ground-based surveys. This paper reviews the utility of a long-term (1984–present) annual aerial monitoring program for submersed aquatic vegetation (SAV) in Chesapeake Bay, its tidal tributaries, and nearby Atlantic coastal bays, USA. We present a series of applications that highlight the program’s importance in assessing anthropogenic impacts, gauging water quality status and trends, establishing and evaluating restoration goals, and understanding the impact of commercial fishing practices on benthic habitats. These examples demonstrate how periodically quantifying coverage of this important foundational habitat answers basic research questions locally, as well as globally, and provides essential information to resource managers. New technologies are enabling more frequent and accurate aerial surveys at greater spatial resolution and lower cost. These advances will support efforts to extend the applications described here to similar issues in other areas.

Predator cues target signaling pathways in toxic algal metabolome - Emily R. Brown; Sam G. Moore; David A. Gaul; Julia Kubanek (Limnology and Oceanography, 2022)
Early detection of predators is critical to the survival of all living organisms. For phytoplankton, recognition and response to chemical cues from predators, as evidence of predation risk, are particularly crucial. The phytoplankton Alexandrium minutum upregulates its toxicity when exposed to copepodamides, a suite of compounds released by copepod predators. However, how A. minutum perceives these predatory cues and what metabolic pathways are involved in initiating toxin induction remains unknown. In this study, liquid chromatography‐mass spectrometry and NMR‐based metabolomics uncovered subtle physiological responses of A. minutum to copepodamides, including altered regulation of branched‐chain amino acid biosynthesis and potential enhancement of butanoate metabolism and arginine biosynthesis. While we have yet to identify a chemoreceptor directly activated by copepod cues, based on the results of inhibition experiments, detection of copepodamides appears to disrupt the activity of serine/threonine phosphatases leading to increased jasmonic acid biosynthesis and signaling, which leads to amplified gonyautoxin biosynthesis in A. minutum . This study is an important step toward a better understanding of chemosensory ecology of predator–prey interactions in phytoplankton.

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Dynamic Habitat Models Reflect Interannual Movement of Cetaceans Within the California Current Ecosystem - Elizabeth A. Becker; Karin A. Forney; David L. Miller; Jay Barlow; Lorenzo Rojas-Bracho; Jorge Urbán R; Jeff E. Moore (Frontiers in Marine Science, 2022)
The distribution of wide-ranging cetacean species often cross national or jurisdictional boundaries, which creates challenges for monitoring populations and managing anthropogenic impacts, especially if data are only available for a portion of the species’ range. Many species found off the U.S. West Coast are known to have continuous distributions into Mexican waters, with highly variable abundance within the U.S. portion of their range. This has contributed to annual variability in design-based abundance estimates from systematic shipboard surveys off the U.S. West Coast, particularly for the abundance of warm temperate species such as striped dolphin, Stenella coeruleoalba , which increases off California during warm-water conditions and decreases during cool-water conditions. Species distribution models (SDMs) can accurately describe shifts in cetacean distribution caused by changing environmental conditions, and are increasingly used for marine species management. However, until recently, data from waters off the Baja California peninsula, México, have not been available for modeling species ranges that span from Baja California to the U.S. West Coast. In this study, we combined data from 1992–2018 shipboard surveys to develop SDMs off the Pacific Coast of Baja California for ten taxonomically diverse cetaceans. We used a Generalized Additive Modeling framework to develop SDMs based on line-transect surveys and dynamic habitat variables from the Hybrid Coordinate Ocean Model (HYCOM). Models were developed for ten species: long- and short-beaked common dolphins ( Delphinus delphis delphis and D. d. bairdii ), Risso’s dolphin ( Grampus griseus ), Pacific white-sided dolphin ( Lagenorhynchus obliquidens ), striped dolphin, common bottlenose dolphin ( Tursiops truncatus ), sperm whale ( Physeter macrocephalus ), blue whale ( Balaenoptera musculus ), fin whale ( B. physalus ), and humpback whale ( Megaptera novaeangliae ). The SDMs provide the first fine-scale (approximately 9 x 9 km grid) estimates of average species density and abundance, including spatially-explicit measures of uncertainty, for waters off the Baja California peninsula. Results provide novel insights into cetacean ecology in this region as well as quantitative spatial data for the assessment and mitigation of anthropogenic impacts.

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

The impacts of HIV infection, age, and education on functional brain networks in adults with HIV - Fan Nils Yang; Shiva Hassanzadeh-Behbahani; Princy Kumar; David J. Moore; Ronald J. Ellis; Xiong Jiang (Journal of NeuroVirology, 2022)

Relationship of the balloon analog risk task to neurocognitive impairment differs by HIV serostatus and history of major depressive disorder - Rowan Saloner; Erin E. Morgan; Mariam A. Hussain; David J. Moore; Robert K. Heaton; Mariana Cherner; Igor Grant; Jennifer E. Iudicello (Journal of NeuroVirology, 2022)
HIV and major depressive disorder (MDD) commonly co-occur and are both linked to greater risk-taking behavior, possibly due to neurocognitive impairment (NCI). The present study examined the concordance of the Balloon Analog Risk Task (BART), a gold standard measure of risk-taking propensity, with NCI and real-world sexual risk behaviors in PWH with comorbid MDD. Participants included 259 adults, stratified by HIV serostatus (HIV + /HIV −) and lifetime MDD (MDD + /MDD −), who completed neuropsychological testing, the BART, and sexual risk behavior questionnaires. Logistic regression, stratified by HIV serostatus, examined joint effects of MDD and BART (linear and quadratic) on NCI. Follow-up linear regressions examined sexual risk behavior and neurocognitive domain T-scores as correlates of the BART. NCI prevalence was lowest in HIV − /MDD − , but BART scores did not differ by HIV/MDD status. In the HIV + group, BART performance predicted NCI such that high and low BART scores related to greater odds of NCI, but only in dual-risk HIV + /MDD + individuals. HIV + /MDD + individuals with both low and high BART scores exhibited poorer learning and recall, whereas processing speed and executive function were only poor in low BART risk-taking HIV + /MDD + . Higher BART scores linearly related to higher sexual risk behaviors only in MDD + individuals, independent of HIV serostatus. Low and high risk-taking on the BART may reflect discrete neurocognitive profiles in HIV + /MDD + individuals, with differential implications for real-world sexual risk behavior. HIV and comorbid MDD may disturb corticostriatal circuits responsible for integrating affective and neurocognitive components of decision-making, thereby contributing to risk-averse and risk-taking phenotypes.

CSF markers of AD-related pathology relate specifically to memory impairment in older people with HIV: a pilot study - Judith D. Lobo; David J. Moore; Mark W. Bondi; Virawudh Soontornniyomkij; Benchawanna Soontornniyomkij; Ben Gouaux; Cristian L. Achim; Ronald J. Ellis; Erin E. Sundermann (Journal of NeuroVirology, 2022)

Birds of a Feather Eat Plastic Together: High Levels of Plastic Ingestion in Great Shearwater Adults and Juveniles Across Their Annual Migratory Cycle - Anna R. Robuck; Christine A. Hudak; Lindsay Agvent; Gwenyth Emery; Peter G. Ryan; Vonica Perold; Kevin D. Powers; Johanna Pedersen; Michael A. Thompson; Justin J. Suca; Michael J. Moore; Craig A. Harms; et al. (Frontiers in Marine Science, 2022)
Limited work to date has examined plastic ingestion in highly migratory seabirds like Great Shearwaters ( Ardenna gravis ) across their entire migratory range. We examined 217 Great Shearwaters obtained from 2008–2019 at multiple locations spanning their yearly migration cycle across the Northwest and South Atlantic to assess accumulation of ingested plastic as well as trends over time and between locations. A total of 2328 plastic fragments were documented in the ventriculus portion of the gastrointestinal tract, with an average of 9 plastic fragments per bird. The mass, count, and frequency of plastic occurrence (FO) varied by location, with higher plastic burdens but lower FO in South Atlantic adults and chicks from the breeding colonies. No fragments of the same size or morphology were found in the primary forage fish prey, the Sand Lance ( Ammodytes spp., n = 202) that supports Great Shearwaters in Massachusetts Bay, United States, suggesting the birds directly ingest the bulk of their plastic loads rather than accumulating via trophic transfer. Fourier-transform infrared spectroscopy indicated that low- and high-density polyethylene were the most common polymers ingested, within all years and locations. Individuals from the South Atlantic contained a higher proportion of larger plastic items and fragments compared to analogous life stages in the NW Atlantic, possibly due to increased use of remote, pelagic areas subject to reduced inputs of smaller, more diverse, and potentially less buoyant plastics found adjacent to coastal margins. Different signatures of polymer type, size, and category between similar life stages at different locations suggests rapid turnover of ingested plastics commensurate with migratory stage and location, though more empirical evidence is needed to ground-truth this hypothesis. This work is the first to comprehensively measure the accumulation of ingested plastics by Great Shearwaters over the last decade and across multiple locations spanning their yearly trans-equatorial migration cycle and underscores their utility as sentinels of plastic pollution in Atlantic ecosystems.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Passive-Sampler-Based Bioavailability Assessment of PCB Congeners Associated with Aroclor-Containing Paint Chips in the Presence of Sediment - Guilherme R. Lotufo; Philip T. Gidley; Andrew D. McQueen; David W. Moore; Deborah A. Edwards; Jeffery Hardenstine; Allen D. Uhler (Archives of Environmental Contamination and Toxicology, 2022)
This is the first investigation of the bioavailability of PCBs associated with paint chips (PC) dispersed in sediment. Bioavailability of PCB-containing PC in sediment was measured using ex situ polyethylene passive samplers (PS) and compared to that of PCBs from field-collected sediments. PC were mixed in freshwater sediment from a relatively uncontaminated site with no known PCB contamination sources and from a contaminated site with non-paint PCB sources. PC

A framework for incorporating ecology into Earth System Models is urgently needed - David J. P. Moore (Global Change Biology, 2022)

Preface: honoring the career of Russell K. Monson - Amy M. Trowbridge; David J. P. Moore; Paul C. Stoy (Oecologia, 2021)

The relationship between vascular endothelial growth factor (VEGF) and amnestic mild cognitive impairment among older adults living with HIV - Vanessa B. Serrano; Jessica L. Montoya; Laura M. Campbell; Erin E. Sundermann; Jennifer Iudicello; Scott Letendre; Robert K. Heaton; David J. Moore (Journal of NeuroVirology, 2021)
Older people with HIV (PWH) experience increased risk of age-related neurodegenerative disorders and cognitive decline, such as amnestic mild cognitive impairment (aMCI). The objective of this study was to examine the relationship between aMCI and plasma VEGF biomarkers among older PWH. Data were collected at a university-based research center from 2011 to 2013. Participants were 67 antiretroviral therapy-treated, virally suppressed PWH. Participants completed comprehensive neurobehavioral and neuromedical evaluations. aMCI status was determined using adapted Jak/Bondi criteria, classifying participants as aMCI + if their performance was > 1 SD below the normative mean on at least two of four memory assessments. VEGF family plasma biomarkers (i.e., VEGF, VEGF-C, VEGF-D, and PIGF) were measured by immunoassay. Logistic regression models were conducted to determine whether VEGF biomarkers were associated with aMCI status. Participants were mostly non-Hispanic white (79%) men (85%) with a mean age of 57.7 years. Eighteen (26.9%) participants met criteria for aMCI. Among potential covariates, only antidepressant drug use differed by aMCI status, and was included as a covariate. VEGF-D was significantly lower in the aMCI + group compared to the aMCI − group. No other VEGF levels (VEGF, VEGF-C, PIGF) differed by aMCI classification ( p s > .05). In a sample of antiretroviral therapy-treated, virally suppressed PWH, lower levels of VEGF-D were associated with aMCI status. Longitudinal analyses in a larger and more diverse sample are needed to support VEGF-D as a putative biological marker of aMCI in HIV.

Trace elements in the shoreline and seabed sediments of the southern Caspian Sea: investigation of contamination level, distribution, ecological and human health risks, and elemental partition coefficient - Mohammad Javad Nematollahi; Behnam Keshavarzi; Farid Moore; Rolf David Vogt; Hassan Nasrollahzadeh Saravi (Environmental Science and Pollution Research, 2021)

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

Saving the Last Unicorns: The Genetic Rescue of Florida’s Pillar Corals - Karen L. Neely; Cynthia L. Lewis; Keri O’Neil; Cheryl M. Woodley; Jennifer Moore; Zach Ransom; Amelia Moura; Ken Nedimyer; David Vaughan (Frontiers in Marine Science, 2021)
As stony coral tissue loss disease (SCTLD) swept through the Florida Reef Tract, one of the most severely impacted species was the iconic pillar coral, Dendrogyra cylindrus . As the species’ population experienced a precipitous decline, a collaborative rescue project collected colony fragments for safekeeping at onshore and offshore nursery facilities. Between 2015 and 2019, a total of 574 fragments representing 128 genotypes were collected. These are currently dispersed among five facilities where they continue to provide opportunities to (1) refine best husbandry practices for D. cylindrus , (2) develop treatment options for SCTLD that have been adapted for use on other species, (3) maximize growth and fragmentation to provide the live tissue needed for eventual restoration, and (4) provide a source of parent colonies for assisted sexual reproduction and new genetic diversity. With the wild pillar coral population in Florida at the end of 2020 at less than 6% of its known 2014 population and continuing to decline, the rescued ex situ colonies represent the entirety of the restoration potential for this species in Florida.

Single-Turnover Variable Chlorophyll Fluorescence as a Tool for Assessing Phytoplankton Photosynthesis and Primary Productivity: Opportunities, Caveats and Recommendations - Nina Schuback; Philippe D. Tortell; Ilana Berman-Frank; Douglas A. Campbell; Aurea Ciotti; Emilie Courtecuisse; Zachary K. Erickson; Tetsuichi Fujiki; Kimberly Halsey; Anna E. Hickman; Yannick Huot; Maxime Y. Gorbunov; et al. (Frontiers in Marine Science, 2021)
Phytoplankton photosynthetic physiology can be investigated through single-turnover variable chlorophyll fluorescence (ST-ChlF) approaches, which carry unique potential to autonomously collect data at high spatial and temporal resolution. Over the past decades, significant progress has been made in the development and application of ST-ChlF methods in aquatic ecosystems, and in the interpretation of the resulting observations. At the same time, however, an increasing number of sensor types, sampling protocols, and data processing algorithms have created confusion and uncertainty among potential users, with a growing divergence of practice among different research groups. In this review, we assist the existing and upcoming user community by providing an overview of current approaches and consensus recommendations for the use of ST-ChlF measurements to examine in-situ phytoplankton productivity and photo-physiology. We argue that a consistency of practice and adherence to basic operational and quality control standards is critical to ensuring data inter-comparability. Large datasets of inter-comparable and globally coherent ST-ChlF observations hold the potential to reveal large-scale patterns and trends in phytoplankton photo-physiology, photosynthetic rates and bottom-up controls on primary productivity. As such, they hold great potential to provide invaluable physiological observations on the scales relevant for the development and validation of ecosystem models and remote sensing algorithms.

Abundance, survival, and annual rate of change of Cuvier's beaked whales ( Ziphius cavirostris ) on a Navy sonar range - K. Alexandra Curtis; Erin A. Falcone; Gregory S. Schorr; Jeffrey E. Moore; David J. Moretti; Jay Barlow; Erin Keene (Marine Mammal Science, 2021)
Bayesian mark‐recapture estimates of survival, abundance, and trend are reported for Cuvier's beaked whales ( Ziphius cavirostris ) using a Navy training range off southern California. The deep‐diving beaked whale family is exceptionally vulnerable to mid‐frequency active sonar (MFAS), which has been implicated in mass strandings and altered foraging behavior. Extremely low sighting probabilities impede studies of population‐level impacts of MFAS on beaked whales. The San Nicolas Basin hosts a Navy training range subject to frequent MFAS use and attracts high densities of Z. cavirostris . An 11‐year (2007–2018) photo‐identification program leveraged automated acoustic detection and location capabilities on the range's 1,800‐km 2 hydrophone array to enhance capture probability. Estimated population parameters for Z. cavirostris using the range included mean (90% credibility intervals) apparent annual survival of 0.950 (0.899–0.986), annual number of individuals as 121 (71–219), and annual rate of change of −0.8% (−5.6%–4.1%). Simulations show the probability of detecting abundance changes is currently low, but can be greatly improved through continued monitoring and increased effort. Complementary data collection on habitat use and demographic rates in San Nicolas and surrounding basins is also essential to relating direct effects of MFAS use to changes in vital rates and broader population outcomes.

Precipitation alters the CO 2 effect on water‐use efficiency of temperate forests - Soumaya Belmecheri; R. Stockton Maxwell; Alan H. Taylor; Kenneth J. Davis; Rossella Guerrieri; David J. P. Moore; Shelly A. Rayback (Global Change Biology, 2021)
Increasing water‐use efficiency (WUE), the ratio of carbon gain to water loss, is a key mechanism that enhances carbon uptake by terrestrial vegetation under rising atmospheric CO 2 ( c a ). Existing theory and empirical evidence suggest a proportional WUE increase in response to rising c a as plants maintain a relatively constant ratio between the leaf intercellular ( c i ) and ambient ( c a ) partial CO 2 pressure ( c i / c a ). This has been hypothesized as the main driver of the strengthening of the terrestrial carbon sink over the recent decades. However, proportionality may not characterize CO 2 effects on WUE on longer time‐scales and the role of climate in modulating these effects is uncertain. Here, we evaluate long‐term WUE responses to c a and climate from 1901 to 2012 CE by reconstructing intrinsic WUE (iWUE, the ratio of photosynthesis to stomatal conductance) using carbon isotopes in tree rings across temperate forests in the northeastern USA. We show that iWUE increased steadily from 1901 to 1975 CE but remained constant thereafter despite continuously rising c a . This finding is consistent with a passive physiological response to c a and coincides with a shift to significantly wetter conditions across the region. Tree physiology was driven by summer moisture at multi‐decadal time‐scales and did not maintain a constant c i / c a in response to rising c a indicating that a point was reached where rising CO 2 had a diminishing effect on tree iWUE. Our results challenge the mechanism, magnitude, and persistence of CO 2 's effect on iWUE with significant implications for projections of terrestrial productivity under a changing climate.

Forest responses to last‐millennium hydroclimate variability are governed by spatial variations in ecosystem sensitivity - Christine R. Rollinson; Andria Dawson; Ann M. Raiho; John W. Williams; Michael C. Dietze; Thomas Hickler; Stephen T. Jackson; Jason McLachlan; David JP Moore; Benjamin Poulter; Tristan Quaife; Jörg Steinkamp; et al. (Ecology Letters, 2021)
Forecasts of future forest change are governed by ecosystem sensitivity to climate change, but ecosystem model projections are under‐constrained by data at multidecadal and longer timescales. Here, we quantify ecosystem sensitivity to centennial‐scale hydroclimate variability, by comparing dendroclimatic and pollen‐inferred reconstructions of drought, forest composition and biomass for the last millennium with five ecosystem model simulations. In both observations and models, spatial patterns in ecosystem responses to hydroclimate variability are strongly governed by ecosystem sensitivity rather than climate exposure. Ecosystem sensitivity was higher in models than observations and highest in simpler models. Model‐data comparisons suggest that interactions among biodiversity, demography and ecophysiology processes dampen the sensitivity of forest composition and biomass to climate variability and change. Integrating ecosystem models with observations from timescales extending beyond the instrumental record can better understand and forecast the mechanisms regulating forest sensitivity to climate variability in a complex and changing world.

Climate sensitivity of understory trees differs from overstory trees in temperate mesic forests - Christine R. Rollinson; M. Ross Alexander; Alex W. Dye; David J. P. Moore; Neil Pederson; Valerie Trouet (Ecology, 2021)
The response of understory trees to climate variability is key to understanding current and future forest dynamics. However, analyses of climatic effects on tree growth have primarily focused on the upper canopy, leaving understory dynamics unresolved. We analyzed differences in climate sensitivity based on canopy position of four common tree species ( Acer rubrum , Fagus grandifolia , Quercus rubra , and Tsuga canadensis ) using growth information from 1,084 trees across eight sites in the northeastern United States. Effects of canopy position on climate response varied, but were significant and often nonlinear, for all four species. Compared to overstory trees, understory trees showed stronger reductions in growth at high temperatures and varied shifts in precipitation response. This contradicts the prevailing assumption that climate responses, particularly to temperature, of understory trees are buffered by the overstory. Forest growth trajectories are uncertain in compositionally and structurally complex forests, and future demography and regeneration dynamics may be misinferred if not all canopy levels are represented in future forecasts.

Effect of tapping for syrup production on sugar maple tree growth in the Quebec Appalachians - Rock Ouimet; François Guillemette; Louis Duchesne; Jean-David Moore (Trees, 2021)

Chronically elevated depressive symptoms interact with acute increases in inflammation to predict worse neurocognition among people with HIV - Rowan Saloner; Emily W. Paolillo; Robert K. Heaton; David J. Grelotti; Murray B. Stein; Andrew H. Miller; J. Hampton Atkinson; Scott L. Letendre; Ronald J. Ellis; Igor Grant; Jennifer E. Iudicello; David J. Moore (Journal of NeuroVirology, 2021)

Sherri Eldridge 1959–2020 - Richard C. Connor; Darlene R. Ketten; Michael J. Moore; Joy S. Reidenberg; Douglas L. Rosene; Tammy Silva; David N. Wiley (Marine Mammal Science, 2021)

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Association of HIV serostatus and metabolic syndrome with neurobehavioral disturbances - Caitlin N. Pope; Jessica L. Montoya; Elizabeth Vasquez; Josué Pérez-Santiago; Ronald Ellis; J. Allen McCutchan; Dilip V. Jeste; David J. Moore; María J. Marquine (Journal of NeuroVirology, 2020)

Predicting biodiversity richness in rapidly changing landscapes: climate, low human pressure or protection as salvation? - David W. Macdonald; Luca Chiaverini; Helen M. Bothwell; Żaneta Kaszta; Eric Ash; Gilmoore Bolongon; Özgün Emre Can; Ahimsa Campos-Arceiz; Phan Channa; Gopalasamy Reuben Clements; Andrew J. Hearn; Laurie Hedges; et al. (Biodiversity and Conservation, 2020)
Rates of biodiversity loss in Southeast Asia are among the highest in the world, and the Indo-Burma and South-Central China Biodiversity Hotspots rank among the world’s most threatened. Developing robust multi-species conservation models is critical for stemming biodiversity loss both here and globally. We used a large and geographically extensive remote-camera survey and multi-scale, multivariate optimization species distribution modelling to investigate the factors driving biodiversity across these two adjoining biodiversity hotspots. Four major findings emerged from the work. (i) We identified clear spatial patterns of species richness, with two main biodiverse centres in the Thai-Malay Peninsula and in the mountainous region of Southwest China. (ii) Carnivores in particular, and large ungulates to a lesser degree, were the strongest indicators of species richness. (iii) Climate had the largest effect on biodiversity, followed by protected status and human footprint. (iv) Gap analysis between the biodiversity model and the current system of protected areas revealed that the majority of areas supporting the highest predicted biodiversity are not protected. Our results highlighted several key locations that should be prioritized for expanding the protected area network to maximize conservation effectiveness. We demonstrated the importance of switching from single-species to multi-species approaches to highlight areas of high priority for biodiversity conservation. In addition, since these areas mostly occur over multiple countries, we also advocate for a paradigmatic focus on transboundary conservation planning.

Mitigating the Legacy Effects of Ditching in a New England Salt Marsh - David M. Burdick; Gregg E. Moore; Susan C. Adamowicz; Geoffrey M. Wilson; Chris R. Peter (Estuaries and Coasts, 2020)

Identifying marine invasion hotspots using stacked species distribution models - Devin A. Lyons; J. Ben Lowen; Thomas W. Therriault; David Brickman; Lanli Guo; Andrea M. Moore; M. Angelica Peña; Zeliang Wang; Claudio DiBacco (Biological Invasions, 2020)

Correction to: A candidate gene study of intermediate histopathological phenotypes in HIV-associated neurocognitive disorders - Andrew J. Levine; Virawudh Soontornniyomkij; Eliezer Masliah; Janet S. Sinsheimer; Sarah S. Ji; Steve Horvath; Elyse J. Singer; Asha Kallianpur; David J. Moore (Journal of NeuroVirology, 2020)

A candidate gene study of intermediate histopathological phenotypes in HIV-associated neurocognitive disorders - Andrew J. Levine; Virawudh Soontornniyomkij; Eliezer Masliah; Janet S. Sinsheimer; Sarah S. Ji; Steve Horvath; Elyse J. Singer; Asha Kallianpur; David J. Moore (Journal of NeuroVirology, 2020)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Adequate supply of dietary taurine stimulates expression of molecular markers of growth and protein turnover in juvenile barramundi (Lates calcarifer) - David A. Poppi; Stephen S. Moore; Nicholas M. Wade; Brett D. Glencross (Fish Physiology and Biochemistry, 2020)

Evaluation of dredged sediment for aquatic placement: interpreting contaminant bioaccumulation - Andrew D. McQueen; Guilherme R. Lotufo; Scott W. Pickard; Andrew M. Lenox; David W. Moore; Katherine von Stackelberg; Burton C. Suedel (Environmental Monitoring and Assessment, 2020)

Design catalogue for eco-engineering of coastal artificial structures: a multifunctional approach for stakeholders and end-users - Kathryn A. O’Shaughnessy; Stephen J. Hawkins; Ally J. Evans; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Robert A. Francis; Simon P. G. Hoggart; Pippa J. Moore; Gregorio Iglesias; David Simmonds; James Ducker; et al. (Urban Ecosystems, 2020)
Coastal urbanisation, energy extraction, food production, shipping and transportation have led to the global proliferation of artificial structures within the coastal and marine environments (sensu “ocean sprawl”), with subsequent loss of natural habitats and biodiversity. To mitigate and compensate impacts of ocean sprawl, the practice of eco-engineering of artificial structures has been developed over the past decade. Eco-engineering aims to create sustainable ecosystems that integrate human society with the natural environment for the benefit of both. The science of eco-engineering has grown markedly, yet synthesis of research into a user-friendly and practitioner-focused format is lacking. Feedback from stakeholders has repeatedly stated that a “photo user guide” or “manual” covering the range of eco-engineering options available for artificial structures would be beneficial. However, a detailed and structured “user guide” for eco-engineering in coastal and marine environments is not yet possible; therefore we present an accessible review and catalogue of trialled eco-engineering options and a summary of guidance for a range of different structures tailored for stakeholders and end-users as the first step towards a structured manual. This work can thus serve as a potential template for future eco-engineering guides. Here we provide suggestions for potential eco-engineering designs to enhance biodiversity and ecosystem functioning and services of coastal artificial structures with the following structures covered: (1) rock revetment, breakwaters and groynes composed of armour stones or concrete units; (2) vertical and sloping seawalls; (3) over-water structures (i.e., piers) and associated support structures; and (4) tidal river walls.

Evaluating spatial patterns in precipitation trends across the Amazon basin driven by land cover and global scale forcings - Nafiseh Haghtalab; Nathan Moore; Brent Porter Heerspink; David W. Hyndman (Theoretical and Applied Climatology, 2020)

Genetic variation in alcohol dehydrogenase is associated with neurocognition in men with HIV and history of alcohol use disorder: preliminary findings - Rowan Saloner; Emily W. Paolillo; Maulika Kohli; Sarah S. Murray; David J. Moore; Igor Grant; Mariana Cherner (Journal of NeuroVirology, 2020)

Pre-frailty predicts cognitive decline at 2-year follow-up in persons living with HIV - Emily W. Paolillo; Ni Sun-Suslow; Elizabeth C. Pasipanodya; Erin E. Morgan; Ronald J. Ellis; Dilip V. Jeste; David J. Moore (Journal of NeuroVirology, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Perennial cover crop influences on soil C and N and maize productivity - Chumki Banik; Cynthia A. Bartel; David A. Laird; Kenneth J. Moore; Andrew W. Lenssen (Nutrient Cycling in Agroecosystems, 2020)

Quantifying Ship Strike Risk to Breeding Whales in a Multiple-Use Marine Park: The Great Barrier Reef - Joshua N. Smith; Natalie Kelly; Simon Childerhouse; Jessica V. Redfern; Thomas J. Moore; David Peel (Frontiers in Marine Science, 2020)

Inflammation-related genes are associated with epigenetic aging in HIV - Erin E. Sundermann; Mariam A. Hussain; David J. Moore; Steven Horvath; David T. S. Lin; Michael S. Kobor; Andrew Levine (Journal of NeuroVirology, 2019)

Associations of regional amyloid-β plaque and phospho-tau pathology with biological factors and neuropsychological functioning among HIV-infected adults - Virawudh Soontornniyomkij; David J. Moore; Ben Gouaux; Benchawanna Soontornniyomkij; Janet S. Sinsheimer; Andrew J. Levine (Journal of NeuroVirology, 2019)

Unexpected discovery of Diadema clarki in the Coral Triangle - Abigail Mary Moore; Asmi Citra Malina Tassakka; Rohani Ambo-Rappe; Inayah Yasir; David John Smith; Jamaluddin Jompa (Marine Biodiversity, 2019)

The current understanding of overlap between characteristics of HIV-associated neurocognitive disorders and Alzheimer’s disease - Leah H. Rubin; Erin E. Sundermann; David J. Moore (Journal of NeuroVirology, 2019)

Potential Effects of Sea-Level Rise on Salt Marsh Elevation Dynamics in a New Hampshire Estuary - Andrew R. Payne; David M. Burdick; Gregg E. Moore (Estuaries and Coasts, 2019)

Linking drought legacy effects across scales: From leaves to tree rings to ecosystems - Steven A. Kannenberg; Kimberly A. Novick; M. Ross Alexander; Justin T. Maxwell; David J. P. Moore; Richard P. Phillips; William R. L. Anderegg (Global Change Biology, 2019)
Severe drought can cause lagged effects on tree physiology that negatively impact forest functioning for years. These “drought legacy effects” have been widely documented in tree‐ring records and could have important implications for our understanding of broader scale forest carbon cycling. However, legacy effects in tree‐ring increments may be decoupled from ecosystem fluxes due to (a) postdrought alterations in carbon allocation patterns; (b) temporal asynchrony between radial growth and carbon uptake; and (c) dendrochronological sampling biases. In order to link legacy effects from tree rings to whole forests, we leveraged a rich dataset from a Midwestern US forest that was severely impacted by a drought in 2012. At this site, we compiled tree‐ring records, leaf‐level gas exchange, eddy flux measurements, dendrometer band data, and satellite remote sensing estimates of greenness and leaf area before, during, and after the 2012 drought. After accounting for the relative abundance of tree species in the stand, we estimate that legacy effects led to ~10% reductions in tree‐ring width increments in the year following the severe drought. Despite this stand‐scale reduction in radial growth, we found that leaf‐level photosynthesis, gross primary productivity (GPP), and vegetation greenness were not suppressed in the year following the 2012 drought. Neither temporal asynchrony between radial growth and carbon uptake nor sampling biases could explain our observations of legacy effects in tree rings but not in GPP. Instead, elevated leaf‐level photosynthesis co‐occurred with reduced leaf area in early 2013, indicating that resources may have been allocated away from radial growth in conjunction with postdrought upregulation of photosynthesis and repair of canopy damage. Collectively, our results indicate that tree‐ring legacy effects were not observed in other canopy processes, and that postdrought canopy allocation could be an important mechanism that decouples tree‐ring signals from GPP.

Self-initiated continuation of and adherence to HIV pre-exposure prophylaxis (PrEP) after PrEP demonstration project roll-off in men who have sex with men: associations with risky decision making, impulsivity/disinhibition, and sensation seeking - Martin Hoenigl; Erin Morgan; Donald Franklin; Peter L. Anderson; Elizabeth Pasipanodya; Matthew Dawson; Marvin Hanashiro; Eric E. Ellorin; Jill Blumenthal; Robert Heaton; David J. Moore; Sheldon R. Morris (Journal of NeuroVirology, 2019)

Correction to: Are soils beneath coniferous tree stands more acidic than soils beneath deciduous tree stands? - Jason R. Burgess-Conforti; Philip A. Moore; Phillip R. Owens; David M. Miller; Amanda J. Ashworth; Phillip D. Hays; Michelle A. Evans-White; Kelsey R. Anderson (Environmental Science and Pollution Research, 2019)

Are soils beneath coniferous tree stands more acidic than soils beneath deciduous tree stands? - Jason R. Burgess-Conforti; Philip A. Moore; Phillip R. Owens; David M. Miller; Amanda J. Ashworth; Phillip D. Hays; Michelle A. Evans-White; Kelsey R. Anderson (Environmental Science and Pollution Research, 2019)

Day length as a key factor moderating the response of coccolithophore growth to elevated p CO 2 - Laura Bretherton; Alex J. Poulton; Tracy Lawson; Nita Rukminasari; Cecilia Balestreri; Declan Schroeder; C. Mark Moore; David J. Suggett (Limnology and Oceanography, 2019)
The fate of coccolithophores in the future oceans remains uncertain, in part due to key factors having not been standardized across experiments. A potentially moderating role for differences in day length (photoperiod) remains largely unexplored. We therefore cultured four different geographical isolates of the species Emiliania huxleyi , as well as two additional species, Gephyrocapsa oceanica (tropical) and Coccolithus braarudii (temperate), to test for interactive effects of p CO 2 with the light : dark (L : D) cycle. We confirmed a general regulatory effect of photoperiod on the p CO 2 response, whereby growth and particulate inorganic carbon and particulate organic carbon (PIC : POC) ratios were reduced with elevated p CO 2 under 14 : 10 h L : D, but these reductions were dampened under continuous (24 h) light. The dynamics underpinning this pattern generally differed for the temperate vs. tropical isolates. Reductions in PIC : POC with elevated p CO 2 for tropical taxa were largely through reduced calcification and enhanced photosynthesis under 14 : 10 h L : D, with differences dampened under continuous light. In contrast, reduced PIC : POC for temperate strains reflected increases of photosynthesis that outpaced increases in calcification rates under 14 : 10 h L : D, with both responses again dampened under continuous light. A multivariate analysis of 35 past studies of E. huxleyi further demonstrated that differences in photoperiod account for as much as 40% (strain B11/92) to 55% (strain NZEH) of the variance in reported p CO 2 ‐induced reductions to growth but not PIC : POC. Our study thus highlights a critical role for day length in moderating the effect of ocean acidification on coccolithophore growth and consequently how this response may play out across latitudes and seasons in future oceans.

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment) - Chantal B. van Houten; Asi Cohen; Dan Engelhard; John P. Hays; Roger Karlsson; Edward Moore; David Fernández; Racheli Kreisberg; Laurence V. Collins; Wouter de Waal; Karin M. de Winter-de Groot; Tom F. W. Wolfs; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Comparative genomics and physiology of the genus Methanohalophilus , a prevalent methanogen in hydraulically fractured shale - Mikayla A. Borton; Rebecca A. Daly; Bridget O'Banion; David W. Hoyt; Daniel N. Marcus; Susan Welch; Sybille S. Hastings; Tea Meulia; Richard A. Wolfe; Anne E. Booker; Shikha Sharma; David R. Cole; et al. (Environmental Microbiology, 2018)
Summary About 60% of natural gas production in the United States comes from hydraulic fracturing of unconventional reservoirs, such as shales or organic‐rich micrites. This process inoculates and enriches for halotolerant microorganisms in these reservoirs over time, resulting in a saline ecosystem that includes methane producing archaea. Here, we survey the biogeography of methanogens across unconventional reservoirs, and report that members of genus Methanohalophilus are recovered from every hydraulically fractured unconventional reservoir sampled by metagenomics. We provide the first genomic sequencing of three isolate genomes, as well as two metagenome assembled genomes (MAGs). Utilizing six other previously sequenced isolate genomes and MAGs, we perform comparative analysis of the 11 genomes representing this genus. This genomic investigation revealed distinctions between surface and subsurface derived genomes that are consistent with constraints encountered in each environment. Genotypic differences were also uncovered between isolate genomes recovered from the same well, suggesting niche partitioning among closely related strains. These genomic substrate utilization predictions were then confirmed by physiological investigation. Fine‐scale microdiversity was observed in CRISPR‐Cas systems of Methanohalophilus , with genomes from geographically distinct unconventional reservoirs sharing spacers targeting the same viral population. These findings have implications for augmentation strategies resulting in enhanced biogenic methane production in hydraulically fractured unconventional reservoirs.

Effect of 1-week betalain-rich beetroot concentrate supplementation on cycling performance and select physiological parameters - Petey W. Mumford; Wesley C. Kephart; Matthew A. Romero; Cody T. Haun; C. Brooks Mobley; Shelby C. Osburn; James C. Healy; Angelique N. Moore; David D. Pascoe; William C. Ruffin; Darren T. Beck; Jeffrey S. Martin; et al. (European Journal of Applied Physiology, 2018)

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.

A composite of multisystem injury and neurocognitive impairment in HIV infection: association with everyday functioning - María J. Marquine; Ilse Flores; Rujvi Kamat; Neco Johnson; Anya Umlauf; Scott Letendre; Dilip Jeste; Igor Grant; David Moore; Robert K. Heaton (Journal of NeuroVirology, 2018)

Geographical CO 2 sensitivity of phytoplankton correlates with ocean buffer capacity - Sophie Richier; Eric P. Achterberg; Matthew P. Humphreys; Alex J. Poulton; David J. Suggett; Toby Tyrrell; Christopher Mark Moore (Global Change Biology, 2018)
Accumulation of anthropogenic CO 2 is significantly altering ocean chemistry. A range of biological impacts resulting from this oceanic CO 2 accumulation are emerging, however, the mechanisms responsible for observed differential susceptibility between organisms and across environmental settings remain obscure. A primary consequence of increased oceanic CO 2 uptake is a decrease in the carbonate system buffer capacity, which characterizes the system's chemical resilience to changes in CO 2 , generating the potential for enhanced variability in p CO 2 and the concentration of carbonate [ ], bicarbonate [ ], and protons [H + ] in the future ocean. We conducted a meta‐analysis of 17 shipboard manipulation experiments performed across three distinct geographical regions that encompassed a wide range of environmental conditions from European temperate seas to Arctic and Southern oceans. These data demonstrated a correlation between the magnitude of natural phytoplankton community biological responses to short‐term CO 2 changes and variability in the local buffer capacity across ocean basin scales. Specifically, short‐term suppression of small phytoplankton ( p CO 2 within experiments performed in regions with higher ambient buffer capacity. The results further highlight the relevance of phytoplankton cell size for the impacts of enhanced p CO 2 in both the modern and future ocean. Specifically, cell size‐related acclimation and adaptation to regional environmental variability, as characterized by buffer capacity, likely influences interactions between primary producers and carbonate chemistry over a range of spatio‐temporal scales.

Climate research priorities for policy-makers, practitioners, and scientists in Georgia, USA - Murray A. Rudd; Althea F. P. Moore; Daniel Rochberg; Lisa Bianchi-Fossati; Marilyn A. Brown; David D’Onofrio; Carrie A. Furman; Jairo Garcia; Ben Jordan; Jennifer Kline; L. Mark Risse; Patricia L. Yager; et al. (Environmental Management, 2018)

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Relative influences of multiple sources of uncertainty on cumulative and incremental tree-ring-derived aboveground biomass estimates - M. Ross Alexander; Christine R. Rollinson; Flurin Babst; Valerie Trouet; David J. P. Moore (Trees, 2018)

Exposure to Sublethal Ammonia Concentrations Alters the Duration and Intensity of Agonistic Interactions in the Crayfish, Orconectes rusticus - David D. Edwards; Katie L. Klotz; Paul A. Moore (Bulletin of Environmental Contamination and Toxicology, 2018)

Evaluating Tidal Wetland Restoration Performance Using National Estuarine Research Reserve System Reference Sites and the Restoration Performance Index (RPI) - Kenneth B. Raposa; Scott Lerberg; Craig Cornu; John Fear; Nina Garfield; Christopher Peter; Robin L.J. Weber; Gregg Moore; David Burdick; Michelle Dionne (Estuaries and Coasts, 2018)

Assessment of wound healing of tagged gray ( Eschrichtius robustus ) and blue ( Balaenoptera musculus ) whales in the eastern North Pacific using long‐term series of photographs - Stephanie A. Norman; Kiirsten R. Flynn; Alexandre N. Zerbini; Frances M. D. Gulland; Michael J. Moore; Stephen Raverty; David S. Rotstein; Bruce R. Mate; Craig Hayslip; Diane Gendron; Richard Sears; Annie B. Douglas; et al. (Marine Mammal Science, 2018)
Tags have been used to examine migration routes and habitat use of large whales for >40 yr, however, evaluation of tag wound healing has largely been short‐term, anecdotal or generalized. This study developed methods for systematic photographic assessment of long‐term external consequences of tag placement, to determine potential differences in wound healing between species and tag types and thus advise future tagging efforts to possibly minimize undesirable side effects. Tag site appearance and healing characteristics were evaluated by two reviewers and a time series evaluated by five veterinarians from photographs during 995 postdeployment encounters with 34 gray and 63 blue whales tagged in the North Pacific. Blue whale resightings were less frequent, but spanned a longer time period due to earlier tag deployments than the more frequent gray whale follow‐up observations. Swelling occurred in 74% of reencountered gray whales, with the highest frequency 6 mo postdeployment. Swellings were common in blue whales with early tag designs but rare with current models. Depressions occurred in 82% of gray and 71% of blue whales. This study demonstrates the value of follow‐up studies of tagged animals and systematic scoring of photographs to quantitatively compare tag response.

Concomitant external pneumatic compression treatment with consecutive days of high intensity interval training reduces markers of proteolysis - Cody T. Haun; Michael D. Roberts; Matthew A. Romero; Shelby C. Osburn; James C. Healy; Angelique N. Moore; Christopher B. Mobley; Paul A. Roberson; Wesley C. Kephart; Petey W. Mumford; Michael D. Goodlett; David D. Pascoe; et al. (European Journal of Applied Physiology, 2017)

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)

Mobile Monitoring of Traumatic Brain Injury in Older Adults: Challenges and Opportunities - Andrei Irimia; Susan Wei; Nanshu Lu; Constance M. Moore; David N. Kennedy (Neuroinformatics, 2017)

Emergent climate and CO 2 sensitivities of net primary productivity in ecosystem models do not agree with empirical data in temperate forests of eastern North America - Christine R. Rollinson; Yao Liu; Ann Raiho; David J. P. Moore; Jason McLachlan; Daniel A. Bishop; Alex Dye; Jaclyn H. Matthes; Amy Hessl; Thomas Hickler; Neil Pederson; Benjamin Poulter; et al. (Global Change Biology, 2017)
Ecosystem models show divergent responses of the terrestrial carbon cycle to global change over the next century. Individual model evaluation and multimodel comparisons with data have largely focused on individual processes at subannual to decadal scales. Thus far, data‐based evaluations of emergent ecosystem responses to climate and CO 2 at multidecadal and centennial timescales have been rare. We compared the sensitivity of net primary productivity ( NPP ) to temperature, precipitation, and CO 2 in ten ecosystem models with the sensitivities found in tree‐ring reconstructions of NPP and raw ring‐width series at six temperate forest sites. These model‐data comparisons were evaluated at three temporal extents to determine whether the rapid, directional changes in temperature and CO 2 in the recent past skew our observed responses to multiple drivers of change. All models tested here were more sensitive to low growing season precipitation than tree‐ring NPP and ring widths in the past 30 years, although some model precipitation responses were more consistent with tree rings when evaluated over a full century. Similarly, all models had negative or no response to warm‐growing season temperatures, while tree‐ring data showed consistently positive effects of temperature. Although precipitation responses were least consistent among models, differences among models to CO 2 drive divergence and ensemble uncertainty in relative change in NPP over the past century. Changes in forest composition within models had no effect on climate or CO 2 sensitivity. Fire in model simulations reduced model sensitivity to climate and CO 2 , but only over the course of multiple centuries. Formal evaluation of emergent model behavior at multidecadal and multicentennial timescales is essential to reconciling model projections with observed ecosystem responses to past climate change. Future evaluation should focus on improved representation of disturbance and biomass change as well as the feedbacks with moisture balance and CO 2 in individual models.

Evaluation of the ROS Inhibiting Activity and Mitochondrial Targeting of Phenolic Compounds in Fibroblast Cells Model System and Enhancement of Efficiency by Natural Deep Eutectic Solvent (NADES) Formulation - Erwann Durand; Jérôme Lecomte; Rashmi Upasani; Béatrice Chabi; Christelle Bayrasy; Bruno Baréa; Elodie Jublanc; Martyn J. Clarke; David J. Moore; Jonathan Crowther; Chantal Wrutniak-Cabello; Pierre Villeneuve (Pharmaceutical Research, 2017)

Articles You Might Have Missed - David C. Watts; Eleanor R. Oakley; Hannah R. Malashock; Elizabeth C. Moore; Frank LoVecchio (Journal of Medical Toxicology, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

Hemodynamic Performance and Thrombogenic Properties of a Superhydrophobic Bileaflet Mechanical Heart Valve - David L. Bark; Hamed Vahabi; Hieu Bui; Sanli Movafaghi; Brandon Moore; Arun K. Kota; Ketul Popat; Lakshmi P. Dasi (Annals of Biomedical Engineering, 2017)

Lifetime methamphetamine dependence is associated with cerebral microgliosis in HIV-1-infected adults - Virawudh Soontornniyomkij; Anya Umlauf; Benchawanna Soontornniyomkij; Isabella B. Batki; David J. Moore; Eliezer Masliah; Cristian L. Achim (Journal of NeuroVirology, 2016)

Vessel strike mitigation lessons from direct observations involving two collisions between noncommercial vessels and North Atlantic right whales ( Eubalaena glacialis ) - David N. Wiley; Charles A. Mayo; Eden Marie Maloney; Michael J. Moore (Marine Mammal Science, 2016)

Comparative genomic, proteomic and exoproteomic analyses of three Pseudomonas strains reveals novel insights into the phosphorus scavenging capabilities of soil bacteria - Ian D. E. A. Lidbury; Andrew R. J. Murphy; David J. Scanlan; Gary D. Bending; Alexandra M. E. Jones; Jonathan D. Moore; Andrew Goodall; John P. Hammond; Elizabeth M. H. Wellington (Environmental Microbiology, 2016)
Summary Bacteria that inhabit the rhizosphere of agricultural crops can have a beneficial effect on crop growth. One such mechanism is the microbial‐driven solubilization and remineralization of complex forms of phosphorus (P). It is known that bacteria secrete various phosphatases in response to low P conditions. However, our understanding of their global proteomic response to P stress is limited. Here, exoproteomic analysis of Pseudomonas putida BIRD‐1 (BIRD‐1), Pseudomonas fluorescens SBW25 and Pseudomonas stutzeri DSM4166 was performed in unison with whole‐cell proteomic analysis of BIRD‐1 grown under phosphate (Pi) replete and Pi deplete conditions. Comparative exoproteomics revealed marked heterogeneity in the exoproteomes of each Pseudomonas strain in response to Pi depletion. In addition to well‐characterized members of the PHO regulon such as alkaline phosphatases, several proteins, previously not associated with the response to Pi depletion, were also identified. These included putative nucleases, phosphotriesterases, putative phosphonate transporters and outer membrane proteins. Moreover, in BIRD‐1, mutagenesis of the master regulator, phoBR , led us to confirm the addition of several novel PHO‐dependent proteins. Our data expands knowledge of the Pseudomonas PHO regulon, including species that are frequently used as bioinoculants, opening up the potential for more efficient and complete use of soil complexed P.

Multilevel analysis of neuropathogenesis of neurocognitive impairment in HIV - Andrew J. Levine; Virawudh Soontornniyomkij; Cristian L. Achim; Eliezer Masliah; Benjamin B. Gelman; Janet S. Sinsheimer; Elyse J. Singer; David J. Moore (Journal of NeuroVirology, 2016)

Accelerated epigenetic aging in brain is associated with pre-mortem HIV-associated neurocognitive disorders - Andrew J. Levine; Austin Quach; David J. Moore; Cristian L. Achim; Virawudh Soontornniyomkij; Eliezer Masliah; Elyse J. Singer; Benjamin Gelman; Natasha Nemanim; Steve Horvath (Journal of NeuroVirology, 2016)

Responses of Marine Organisms to Climate Change across Oceans - Elvira S. Poloczanska; Michael T. Burrows; Christopher J. Brown; Jorge García Molinos; Benjamin S. Halpern; Ove Hoegh-Guldberg; Carrie V. Kappel; Pippa J. Moore; Anthony J. Richardson; David S. Schoeman; William J. Sydeman (Frontiers in Marine Science, 2016)

Drag from fishing gear entangling North Atlantic right whales - Julie M. van der Hoop; Peter Corkeron; John Kenney; Scott Landry; David Morin; Jamison Smith; Michael J. Moore (Marine Mammal Science, 2016)
Lethal and sublethal fishing gear entanglement is pervasive in North Atlantic right whales ( Eubalaena glacialis ). Entanglement can lead to direct injury and is likely to incur substantial energetic costs. This study (1) evaluates drag characteristics of entangled right whales, (2) contextualizes gear drag measurements for individual whales, and (3) quantifies the benefits of partial disentanglement. A load cell measured drag forces on 15 sets of fishing gear removed from entangled right whales, a towed satellite telemetry buoy, and 200 m of polypropylene line as it was shortened to 25 m, as they were towed behind a vessel at ~0.77, 1.3, and 2.1 m/s (~1.5, 2.5, and 4 knots) and ~0, 3, and 6 m depth. Mean drag ranges from 8.5 N to 315 N, and can be predicted from the dry weight or length of the gear. Combining gear drag measurements with theoretical estimates of drag on whales' bodies suggests that on average, entanglement increases drag and propulsive power by 1.47 fold. Reducing trailing line length by 75% can reduce parasitic gear drag by 85%, reinforcing current disentanglement response practices. These drag measurements can be incorporated into disentanglement response, serious injury determination, and evaluation of sublethal effects on population dynamics.

A Comparison of Structural Brain Imaging Findings in Autism Spectrum Disorder and Attention-Deficit Hyperactivity Disorder - Chase C. Dougherty; David W. Evans; Scott M. Myers; Gregory J. Moore; Andrew M. Michael (Neuropsychology Review, 2016)

Evaluation of a new screening-level risk assessment tool applied to non-indigenous marine invertebrates in Canadian coastal waters - David Drolet; Claudio DiBacco; Andrea Locke; Cynthia H. McKenzie; Christopher W. McKindsey; Andrea M. Moore; Janis L. Webb; Thomas W. Therriault (Biological Invasions, 2016)

Quantifying the conservation value of seascape connectivity: a global synthesis - Andrew D. Olds; Rod M. Connolly; Kylie A. Pitt; Simon J. Pittman; Paul S. Maxwell; Chantal M. Huijbers; Brad R. Moore; Simon Albert; David Rissik; Russell C. Babcock; Thomas A. Schlacher (Global Ecology and Biogeography, 2016)
Aim Connectivity structures populations, communities and ecosystems in the sea. The extent of connectivity is, therefore, predicted to also influence the outcomes of conservation initiatives, such as marine reserves. Here we review the published evidence about how important seascape connectivity (i.e. landscape connectivity in the sea) is for marine conservation outcomes. Location Global. Methods We analysed the global literature on the effects of seascape connectivity on reserve performance. Results In the majority of cases, greater seascape connectivity inside reserves translates into better conservation outcomes (i.e. enhanced productivity and diversity). Research on reserve performance is, however, most often conducted separately from research on connectivity, resulting in few studies ( Main conclusions Given that research rarely connects the effects of connectivity and reserves, our thesis is that stronger linkages between landscape ecology and marine spatial planning are likely to improve conservation outcomes in the sea. The key science challenge is to identify the full range of ecological functions that are modulated by connectivity and the spatial scale over which these functions enhance conservation outcomes.

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Biofilm formation in an experimental water distribution system: the contamination of non-touch sensor taps and the implication for healthcare - Ginny Moore; David Stevenson; Katy-Anne Thompson; Simon Parks; Didier Ngabo; Allan M. Bennett; Jimmy T. Walker (Biofouling, 2015)

When the Tides Don’t Turn: Floodgates and Hypoxic Zones in the Lower Fraser River, British Columbia, Canada - Jennifer Gordon; Michael Arbeider; David Scott; Samantha M. Wilson; Jonathan W. Moore (Estuaries and Coasts, 2015)

Ischemic Stroke Patients with Active Malignancy or Extracardiac Shunts Are More Likely to Have a Right-to-Left Shunt Found by TCD Than Echocardiogram - Adam de Havenon; Anne Moore; Ali Sultan-Qurraie; Jennifer J. Majersik; Greg Stoddard; David Tirschwell (Translational Stroke Research, 2015)

Microneedle characterisation: the need for universal acceptance criteria and GMP specifications when moving towards commercialisation - Rebecca E. M. Lutton; Jessica Moore; Eneko Larrañeta; Stephen Ligett; A. David Woolfson; Ryan F. Donnelly (Drug Delivery and Translational Research, 2015)

Comparison of low-carbon pathways for California - Geoffrey M. Morrison; Sonia Yeh; Anthony R. Eggert; Christopher Yang; James H. Nelson; Jeffery B. Greenblatt; Raphael Isaac; Mark Z. Jacobson; Josiah Johnston; Daniel M. Kammen; Ana Mileva; Jack Moore; et al. (Climatic Change, 2015)

Local Quantification of Wall Thickness and Intraluminal Thrombus Offer Insight into the Mechanical Properties of the Aneurysmal Aorta - Giampaolo Martufi; Alessandro Satriano; Randy D. Moore; David A. Vorp; Elena S. Di Martino (Annals of Biomedical Engineering, 2015)

Advancing Product Quality: a Summary of the Inaugural FDA/PQRI Conference - Lawrence X. Yu; Jeffrey Baker; Susan C. Berlam; Ashley Boam; E. J. Brandreth; Lucinda Buhse; Thomas Cosgrove; David Doleski; Lynne Ensor; Joseph Famulare; Mohan Ganapathy; Gustavo Grampp; et al. (The AAPS Journal, 2015)

Social Cognition and Brain Morphology: Implications for Developmental Brain Dysfunction - David W. Evans; Steven M. Lazar; K. B. Boomer; Aaron D. Mitchel; Andrew M. Michael; Gregory J. Moore (Brain Imaging and Behavior, 2015)

A new data architecture for advancing life cycle assessment - Wesley W. Ingwersen; Troy R. Hawkins; Thomas R. Transue; David E. Meyer; Gary Moore; Ezra Kahn; Peter Arbuckle; Heidi Paulsen; Gregory A. Norris (The International Journal of Life Cycle Assessment, 2015)

Changes in soil biogeochemistry following disturbance by girdling and mountain pine beetles in subalpine forests - Nicole A. Trahan; Emily L. Dynes; Evan Pugh; David J. P. Moore; Russell K. Monson (Oecologia, 2015)

Volcanic ash supply to the surface ocean—remote sensing of biological responses and their wider biogeochemical significance - Thomas J. Browning; Katherine Stone; Heather A. Bouman; Tamsin A. Mather; David M. Pyle; C. Mark Moore; Victor Martinez-Vicente (Frontiers in Marine Science, 2015)

Questioning the use of an amphibian colour morph as an indicator of climate change - Jean‐David Moore; Martin Ouellet (Global Change Biology, 2015)
The effects of recent climate changes on earth ecosystems are likely among the most important ecological concerns in human history. Good bioindicators are essential to properly assess the magnitude of these changes. In the last decades, studies have suggested that the morph proportion of the eastern red‐backed salamander (Plethodon cinereus), one of the most widely distributed and abundant vertebrate species in forests of eastern North America, could be used as a proxy for monitoring climate changes. Based on new discoveries in the northern areas of the species' range and on one of the largest compilation ever made for a vertebrate in North America (236 109 observations compiled from 1880 to 2013 in 1148 localities), we demonstrate however that climatic and geographic variables do not influence the colour morph proportions in P. cinereus populations. Consequently, we show that the use of colour morph proportions of this species do not perform as an indicator of climate change. Our findings indicate that bioindicator paradigms can be significantly challenged by new ecological research and more representative databases.

Emergent stability in a large, free‐flowing watershed - Jonathan W. Moore; Michael P. Beakes; Holly K. Nesbitt; Justin D. Yeakel; David A. Patterson; Lisa A. Thompson; Corey C. Phillis; Douglas C. Braun; Corinna Favaro; David Scott; Charmaine Carr-Harris; William I. Atlas (Ecology, 2015)
While it is widely recognized that financial stock portfolios can be stabilized through diverse investments, it is also possible that certain habitats can function as natural portfolios that stabilize ecosystem processes. Here we propose and examine the hypothesis that free‐flowing river networks act as such portfolios and confer stability through their integration of upstream geological, hydrological, and biological diversity. We compiled a spatially (142 sites) and temporally (1980–present) extensive data set on fisheries, water flows, and temperatures, from sites within one of the largest watersheds in the world that remains without dams on its mainstem, the Fraser River, British Columbia, Canada. We found that larger catchments had more stable fisheries catches, water flows, and water temperatures than smaller catchments. These data provide evidence that free‐flowing river networks function as hierarchically nested portfolios with stability as an emergent property. Thus, free‐flowing river networks can represent a natural system for buffering variation and extreme events.

Strengthening confidence in climate change impact science - Mary I. O'Connor; Johnna M. Holding; Carrie V. Kappel; Carlos M. Duarte; Keith Brander; Christopher J. Brown; John F. Bruno; Lauren Buckley; Michael T. Burrows; Benjamin S. Halpern; Wolfgang Kiessling; Pippa Moore; et al. (Global Ecology and Biogeography, 2015)
Aim To assess confidence in conclusions about climate‐driven biological change through time, and identify approaches for strengthening confidence scientific conclusions about ecological impacts of climate change. Location Global. Methods We outlined a framework for strengthening confidence in inferences drawn from biological climate impact studies through the systematic integration of prior expectations, long‐term data and quantitative statistical procedures. We then developed a numerical confidence index ( C index ) and used it to evaluate current practices in 208 studies of marine climate impacts comprising 1735 biological time series. Results Confidence scores for inferred climate impacts varied widely from 1 to 16 (very low to high confidence). Approximately 35% of analyses were not associated with clearly stated prior expectations and 65% of analyses did not test putative non‐climate drivers of biological change. Among the highest‐scoring studies, 91% tested prior expectations, 86% formulated expectations for alternative drivers but only 63% statistically tested them. Higher confidence scores observed in studies that did not detect a change or tracked multiple species suggest publication bias favouring impact studies that are consistent with climate change. The number of time series showing climate impacts was a poor predictor of average confidence scores for a given group, reinforcing that vote‐counting methodology is not appropriate for determining overall confidence in inferences. Main conclusions Climate impacts research is expected to attribute biological change to climate change with measurable confidence. Studies with long‐term, high‐resolution data, appropriate statistics and tests of alternative drivers earn higher C index scores, suggesting these should be given greater weight in impact assessments. Together with our proposed framework, the results of our C index analysis indicate how the science of detecting and attributing biological impacts to climate change can be strengthened through the use of evidence‐based prior expectations and thorough statistical analyses, even when data are limited, maximizing the impact of the diverse and growing climate change ecology literature.

Fire in Australian savannas: from leaf to landscape - Jason Beringer; Lindsay B. Hutley; David Abramson; Stefan K. Arndt; Peter Briggs; Mila Bristow; Josep G. Canadell; Lucas A. Cernusak; Derek Eamus; Andrew C. Edwards; Bradley J. Evans; Benedikt Fest; et al. (Global Change Biology, 2015)
Savanna ecosystems comprise 22% of the global terrestrial surface and 25% of Australia (almost 1.9 million km 2 ) and provide significant ecosystem services through carbon and water cycles and the maintenance of biodiversity. The current structure, composition and distribution of Australian savannas have coevolved with fire, yet remain driven by the dynamic constraints of their bioclimatic niche. Fire in Australian savannas influences both the biophysical and biogeochemical processes at multiple scales from leaf to landscape. Here, we present the latest emission estimates from Australian savanna biomass burning and their contribution to global greenhouse gas budgets. We then review our understanding of the impacts of fire on ecosystem function and local surface water and heat balances, which in turn influence regional climate. We show how savanna fires are coupled to the global climate through the carbon cycle and fire regimes. We present new research that climate change is likely to alter the structure and function of savannas through shifts in moisture availability and increases in atmospheric carbon dioxide, in turn altering fire regimes with further feedbacks to climate. We explore opportunities to reduce net greenhouse gas emissions from savanna ecosystems through changes in savanna fire management.

Epigenome-Wide Association Study for Parkinson’s Disease - Kerry Moore; Amy Jayne McKnight; David Craig; Francis O’Neill (NeuroMolecular Medicine, 2014)

Mapping migration in a songbird using high‐resolution genetic markers - Kristen C. Ruegg; Eric C. Anderson; Kristina L. Paxton; Vanessa Apkenas; Sirena Lao; Rodney B. Siegel; David F. DeSante; Frank Moore; Thomas B. Smith (Molecular Ecology, 2014)
Neotropic migratory birds are declining across the W estern H emisphere, but conservation efforts have been hampered by the inability to assess where migrants are most limited—the breeding grounds, migratory stopover sites or wintering areas. A major challenge has been the lack of an efficient, reliable and broadly applicable method for measuring the strength of migratory connections between populations across the annual cycle. Here, we show how high‐resolution genetic markers can be used to identify genetically distinct groups of a migratory bird, the W ilson's warbler ( C ardellina pusilla ), at fine enough spatial scales to facilitate assessing regional drivers of demographic trends. By screening 1626 samples using 96 highly divergent single nucleotide polymorphisms selected from a large pool of candidates (~450 000), we identify novel region‐specific migratory routes and timetables of migration along the P acific F lyway. Our results illustrate that high‐resolution genetic markers are more reliable, precise and amenable to high throughput screening than previously described intrinsic marking techniques, making them broadly applicable to large‐scale monitoring and conservation of migratory organisms.

A tree-ring perspective on the terrestrial carbon cycle - Flurin Babst; M. Ross Alexander; Paul Szejner; Olivier Bouriaud; Stefan Klesse; John Roden; Philippe Ciais; Benjamin Poulter; David Frank; David J. P. Moore; Valerie Trouet (Oecologia, 2014)

Real Exposure: Field Measurement of Chemical Plumes in Headwater Streams - David D. Edwards; Paul A. Moore (Archives of Environmental Contamination and Toxicology, 2014)

The influence of stem guying on radial growth, stem form and internal resin features in radiata pine - John R. Moore; David J. Cown; John R. Lee; Russell B. McKinley; Rod K. Brownlie; Trevor G. Jones; Geoffrey M. Downes (Trees, 2014)

Hematological, biochemical, and morphological parameters as prognostic indicators for stranded common dolphins ( Delphinus delphis) from Cape Cod, Massachusetts, U.S.A. - Sarah M. Sharp; Joyce S. Knoll; Michael J. Moore; Kathleen M. Moore; Charles T. Harry; Jane M. Hoppe; Misty E. Niemeyer; Ian Robinson; Kathryn S. Rose; W. Brian Sharp; David Rotstein (Marine Mammal Science, 2014)
The current paucity of published blood values and other clinically relevant data for short‐beaked common dolphins, Delphinus delphis, hinders the ability of veterinarians and responders to make well‐informed diagnoses and disposition decisions regarding live strandings of this species. This study examined hematologic, clinical chemistry, and physical parameters from 26 stranded common dolphins on Cape Cod, Massachusetts, in light of their postrelease survival data to evaluate each parameter's efficacy as a prognostic indicator. Statistically and clinically significant differences were found between failed and survived dolphins, including lower hematocrit, hemoglobin, TCO 2 , and bicarbonate and higher blood urea nitrogen, uric acid, and length‐to‐girth ratios in animals that failed. In general when compared to survivors, failed dolphins exhibited acidosis, dehydration, lower PCV s, and decreased body condition. Additionally, failed dolphins had the highest ALT , AST , CK , LDH , GGT , and lactate values. These blood values combined with necropsy findings indicate that there are likely a variety of factors affecting postrelease survival, including both preexisting illness and stranding‐induced conditions such as capture myopathy. Closer evaluation of these parameters for stranded common dolphins on point of care analyzers in the field may allow stranding personnel to make better disposition decisions in the future.

A synthesis of methane emissions from 71 northern, temperate, and subtropical wetlands - Merritt R. Turetsky; Agnieszka Kotowska; Jill Bubier; Nancy B. Dise; Patrick Crill; Ed R. C. Hornibrook; Kari Minkkinen; Tim R. Moore; Isla H. Myers‐Smith; Hannu Nykänen; David Olefeldt; Janne Rinne; et al. (Global Change Biology, 2014)
Wetlands are the largest natural source of atmospheric methane. Here, we assess controls on methane flux using a database of approximately 19 000 instantaneous measurements from 71 wetland sites located across subtropical, temperate, and northern high latitude regions. Our analyses confirm general controls on wetland methane emissions from soil temperature, water table, and vegetation, but also show that these relationships are modified depending on wetland type (bog, fen, or swamp), region (subarctic to temperate), and disturbance. Fen methane flux was more sensitive to vegetation and less sensitive to temperature than bog or swamp fluxes. The optimal water table for methane flux was consistently below the peat surface in bogs, close to the peat surface in poor fens, and above the peat surface in rich fens. However, the largest flux in bogs occurred when dry 30‐day averaged antecedent conditions were followed by wet conditions, while in fens and swamps, the largest flux occurred when both 30‐day averaged antecedent and current conditions were wet. Drained wetlands exhibited distinct characteristics, e.g. the absence of large flux following wet and warm conditions, suggesting that the same functional relationships between methane flux and environmental conditions cannot be used across pristine and disturbed wetlands. Together, our results suggest that water table and temperature are dominant controls on methane flux in pristine bogs and swamps, while other processes, such as vascular transport in pristine fens, have the potential to partially override the effect of these controls in other wetland types. Because wetland types vary in methane emissions and have distinct controls, these ecosystems need to be considered separately to yield reliable estimates of global wetland methane release.

Safety and Efficacy of Flumazenil for Reversal of Iatrogenic Benzodiazepine-Associated Delirium Toxicity During Treatment of Alcohol Withdrawal, a Retrospective Review at One Center - Philip W. Moore; J Ward Donovan; Keith K. Burkhart; Jeffrey A. Waskin; Michelle A. Hieger; Audrey R. Adkins; Yijin Wert; David A. Haggerty; J. J. Rasimas (Journal of Medical Toxicology, 2014)

Genetic analysis of quantitative phenotypes in AD and MCI: imaging, cognition and biomarkers - Li Shen; Paul M. Thompson; Steven G. Potkin; Lars Bertram; Lindsay A. Farrer; Tatiana M. Foroud; Robert C. Green; Xiaolan Hu; Matthew J. Huentelman; Sungeun Kim; John S. K. Kauwe; Qingqin Li; et al. (Brain Imaging and Behavior, 2014)

An active lifestyle is associated with better neurocognitive functioning in adults living with HIV infection - Pariya L. Fazeli; Steven Paul Woods; Robert K. Heaton; Anya Umlauf; Ben Gouaux; Debra Rosario; Raeanne C. Moore; Igor Grant; David J. Moore (Journal of NeuroVirology, 2014)

FXR-induced secretion of FGF15/19 inhibits CYP27 expression in cholangiocytes through p38 kinase pathway - Dongju Jung; J. Philippe York; Li Wang; Chaofeng Yang; Aijun Zhang; Heather L. Francis; Paul Webb; Wallace L. McKeehan; Gianfranco Alpini; Gene D. LeSage; David D. Moore; Xuefeng Xia (Pflügers Archiv - European Journal of Physiology, 2014)

AutoGate: automating analysis of flow cytometry data - Stephen Meehan; Guenther Walther; Wayne Moore; Darya Orlova; Connor Meehan; David Parks; Eliver Ghosn; Megan Philips; Erin Mitsunaga; Jeffrey Waters; Aaron Kantor; Ross Okamura; et al. (Immunologic Research, 2014)

In situ validation of MERIS marine reflectance off the southwest Iberian Peninsula: assessment of vicarious adjustment and corrections for near-land adjacency - Sónia Cláudia Vitorino Cristina; Gerald Francis Moore; Priscila Raquel Fernandes Costa Goela; John David Icely; Alice Newton (International Journal of Remote Sensing, 2014)

Impacts of Varying Estuarine Temperature and Light Conditions on Zostera marina (Eelgrass) and its Interactions With Ruppia maritima (Widgeongrass) - Kenneth A. Moore; Erin C. Shields; David B. Parrish (Estuaries and Coasts, 2014)

Mercury in bats from the northeastern United States - David E. Yates; Evan M. Adams; Sofia E. Angelo; David C. Evers; John Schmerfeld; Marianne S. Moore; Thomas H. Kunz; Timothy Divoll; Samuel T. Edmonds; Christopher Perkins; Robert Taylor; Nelson J. O’Driscoll (Ecotoxicology, 2014)

Behavioral impacts of disentanglement of a right whale under sedation and the energetic cost of entanglement - Julie van der Hoop; Michael Moore; Andreas Fahlman; Alessandro Bocconcelli; Clay George; Katharine Jackson; Carolyn Miller; David Morin; Thomas Pitchford; Teri Rowles; Jamison Smith; Barb Zoodsma (Marine Mammal Science, 2014)
Protracted entanglement in fishing gear often leads to emaciation through reduced mobility and foraging ability, and energy budget depletion from the added drag of towing gear for months or years. We examined changes in kinematics of a tagged entangled North Atlantic right whale (Eg 3911), before, during, and after disentanglement on 15 January 2011. To calculate the additional drag forces and energetic demand associated with various gear configurations, we towed three sets of gear attached to a load‐cell tensiometer at multiple speeds. Tag analyses revealed significant increases in dive depth and duration; ascent, descent and fluke stroke rates; and decreases in root mean square fluke amplitude (a proxy for thrust) following disentanglement. Conservative drag coefficients while entangled in all gear configurations (mean ± SD C d,e,go = 3.4 × 10 −3 ± 0.0003, C d,e,gb = 3.7 × 10 −3 ± 0.0003, C d,e,sl = 3.8 × 10 −3 ± 0.0004) were significantly greater than in the nonentangled case ( C d,n = 3.2 × 10 −3 ± 0.0003; P = 0.0156, 0.0312, 0.0078, respectively). Increases in total power input (including standard metabolism) over the nonentangled condition ranged from 1.6% to 120.9% for all gear configurations tested; locomotory power requirements increased 60.0%–164.6%. These results highlight significant alteration to swimming patterns, and the magnitude of energy depletion in a chronically entangled whale.

Modulation of BK Channel by MicroRNA-9 in Neurons After Exposure to HIV and Methamphetamine - Erick T. Tatro; Shannon Hefler; Stephanie Shumaker-Armstrong; Benchawanna Soontornniyomkij; Michael Yang; Alex Yermanos; Nina Wren; David J. Moore; Cristian L. Achim (Journal of Neuroimmune Pharmacology, 2013)

Real-world impact of neurocognitive deficits in acute and early HIV infection - Katie L. Doyle; Erin E. Morgan; Sheldon Morris; Davey M. Smith; Susan Little; Jennifer E. Iudicello; Kaitlin Blackstone; David J. Moore; Igor Grant; Scott L. Letendre; Steven Paul Woods (Journal of NeuroVirology, 2013)

Factors influencing the movement biology of migrant songbirds confronted with an ecological barrier - Jaclyn A. Smolinsky; Robert H. Diehl; Thomas A. Radzio; David K. Delaney; Frank R. Moore (Behavioral Ecology and Sociobiology, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Physical exercise is associated with less neurocognitive impairment among HIV-infected adults - Catherine A. Dufour; Maria J. Marquine; Pariya L. Fazeli; Brook L. Henry; Ronald J. Ellis; Igor Grant; David J. Moore (Journal of NeuroVirology, 2013)

Persistent reduced ecosystem respiration after insect disturbance in high elevation forests - David J. P. Moore; Nicole A. Trahan; Phil Wilkes; Tristan Quaife; Britton B. Stephens; Kelly Elder; Ankur R. Desai; Jose Negron; Russell K. Monson (Ecology Letters, 2013)
Amid a worldwide increase in tree mortality, mountain pine beetles ( Dendroctonus ponderosae Hopkins) have led to the death of billions of trees from Mexico to Alaska since 2000. This is predicted to have important carbon, water and energy balance feedbacks on the Earth system. Counter to current projections, we show that on a decadal scale, tree mortality causes no increase in ecosystem respiration from scales of several square metres up to an 84 km 2 valley. Rather, we found comparable declines in both gross primary productivity and respiration suggesting little change in net flux, with a transitory recovery of respiration 6–7 years after mortality associated with increased incorporation of leaf litter C into soil organic matter, followed by further decline in years 8–10. The mechanism of the impact of tree mortality caused by these biotic disturbances is consistent with reduced input rather than increased output of carbon.

Myeloid cell HIF-1α regulates asthma airway resistance and eosinophil function - Laura E. Crotty Alexander; Kathryn Akong-Moore; Stephanie Feldstein; Per Johansson; Anh Nguyen; Elisa K. McEachern; Shari Nicatia; Andrew S. Cowburn; Joshua Olson; Jae Youn Cho; Hart Isaacs; Randall S. Johnson; et al. (Journal of Molecular Medicine, 2013)

Rope trauma, sedation, disentanglement, and monitoring‐tag associated lesions in a terminally entangled North Atlantic right whale ( Eubalaena glacialis ) - Michael Moore; Russel Andrews; Trevor Austin; James Bailey; Alex Costidis; Clay George; Katie Jackson; Tom Pitchford; Scott Landry; Allan Ligon; William McLellan; David Morin; et al. (Marine Mammal Science, 2013)
A chronically entangled North Atlantic right whale, with consequent emaciation was sedated, disentangled to the extent possible, administered antibiotics, and satellite tag tracked for six subsequent days. It was found dead 11 d after the tag ceased transmission. Chronic constrictive deep rope lacerations and emaciation were found to be the proximate cause of death, which may have ultimately involved shark predation. A broadhead cutter and a spring‐loaded knife used for disentanglement were found to induce moderate wounds to the skin and blubber. The telemetry tag, with two barbed shafts partially penetrating the blubber was shed, leaving barbs embedded with localized histological reaction. One of four darts administered shed the barrel, but the needle was found postmortem in the whale with an 80º bend at the blubber‐muscle interface. This bend occurred due to epaxial muscle movement relative to the overlying blubber, with resultant necrosis and cavitation of underlying muscle. This suggests that rigid, implanted devices that span the cetacean blubber muscle interface, where the muscle moves relative to the blubber, could have secondary health impacts. Thus we encourage efforts to develop new tag telemetry systems that do not penetrate the subdermal sheath, but still remain attached for many months.

Substance use is a risk factor for neurocognitive deficits and neuropsychiatric distress in acute and early HIV infection - Erica Weber; Erin E. Morgan; Jennifer E. Iudicello; Kaitlin Blackstone; Igor Grant; Ronald J. Ellis; Scott L. Letendre; Susan Little; Sheldon Morris; Davey M. Smith; David J. Moore; Steven Paul Woods (Journal of NeuroVirology, 2013)

Shark predation on North Atlantic right whales ( Eubalaena glacialis ) in the southeastern United States calving ground - Jessica K. D. Taylor; John W. Mandelman; William A. McLellan; Michael J. Moore; Gregory B. Skomal; David S. Rotstein; Scott D. Kraus (Marine Mammal Science, 2013)

Stream community and ecosystem responses to the boom and bust of an invading snail - Jonathan W. Moore; David B. Herbst; Walter N. Heady; Stephanie M. Carlson (Biological Invasions, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Antioxidant Sestrin-2 Redistribution to Neuronal Soma in Human Immunodeficiency Virus-Associated Neurocognitive Disorders - Virawudh Soontornniyomkij; Benchawanna Soontornniyomkij; David J. Moore; Ben Gouaux; Eliezer Masliah; Spencer Tung; Harry V. Vinters; Igor Grant; Cristian L. Achim (Journal of Neuroimmune Pharmacology, 2012)

Contractility assessment in enzymatically isolated cardiomyocytes - Carlos Bazan; David Torres Barba; Trevor Hawkins; Hung Nguyen; Samantha Anderson; Esteban Vazquez-Hidalgo; Rosa Lemus; J’Terrell Moore; Jeremy Mitchell; Johanna Martinez; Delnita Moore; Jessica Larsen; et al. (Biophysical Reviews, 2012)

Increased cortical expression of FK506 binding protein-51 in HIV-associated neurocognitive disorders - Virawudh Soontornniyomkij; Ian P. Everall; David J. Moore; Ben Gouaux; Erick T. Tatro; Vadim Gospodarev; Eliezer Masliah; Nicole S. Yin; Harry V. Vinters; Cristian L. Achim (Journal of NeuroVirology, 2012)

Using aerial photography to investigate evidence of feeding by bowhead whales - Julie A. Mocklin; David J. Rugh; Sue E. Moore; Robyn P. Angliss (Marine Mammal Science, 2012)
Aerial photographs were analyzed to investigate the feeding habits of the Bering‐Chukchi‐Beaufort (BCB) population of bowhead whales ( Balaena mysticetus ), particularly epibenthic feeding near Barrow, Alaska. Evidence of epibenthic feeding was based on mud visible on the dorsal surface of whales, resulting from feeding near the seafloor. Other cues used to assess feeding were an open mouth or the presence of feces in photographs. Over 3,600 photographs were analyzed including photos from surveys in spring and late summer and in both the western and eastern Beaufort Sea. Of all the photographs analyzed, 64% were scored as definitively muddy. In spring, ratios ranged from a low of 27% in 2003 to a high of 76% in 2004. When all May sample sets off Barrow were combined (1985, 1986, 2003, 2004), there was a significant difference ( t ‐test, P

Above‐ and belowground responses of arctic tundra ecosystems to altered soil nutrients and mammalian herbivory - Laura Gough; John C. Moore; Gauis R. Shaver; Rodney T. Simpson; David R. Johnson (Ecology, 2012)
Theory and observation indicate that changes in the rate of primary production can alter the balance between the bottom‐up influences of plants and resources and the top‐down regulation of herbivores and predators on ecosystem structure and function. The Exploitation Ecosystem Hypothesis (EEH) posited that as aboveground net primary productivity (ANPP) increases, the additional biomass should support higher trophic levels. We developed an extension of EEH to include the impacts of increases in ANPP on belowground consumers in a similar manner as aboveground, but indirectly through changes in the allocation of photosynthate to roots. We tested our predictions for plants aboveground and for phytophagous nematodes and their predators belowground in two common arctic tundra plant communities subjected to 11 years of increased soil nutrient availability and/or exclusion of mammalian herbivores. The less productive dry heath (DH) community met the predictions of EEH aboveground, with the greatest ANPP and plant biomass in the fertilized plots protected from herbivory. A palatable grass increased in fertilized plots while dwarf evergreen shrubs and lichens declined. Belowground, phytophagous nematodes also responded as predicted, achieving greater biomass in the higher ANPP plots, whereas predator biomass tended to be lower in those same plots (although not significantly). In the higher productivity moist acidic tussock (MAT) community, aboveground responses were quite different. Herbivores stimulated ANPP and biomass in both ambient and enriched soil nutrient plots; maximum ANPP occurred in fertilized plots exposed to herbivory. Fertilized plots became dominated by dwarf birch (a deciduous shrub) and cloudberry (a perennial forb); under ambient conditions these two species coexist with sedges, evergreen dwarf shrubs, and Sphagnum mosses. Phytophagous nematodes did not respond significantly to changes in ANPP, although predator biomass was greatest in control plots. The contrasting results of these two arctic tundra plant communities suggest that the predictions of EEH may hold for very low ANPP communities, but that other factors, including competition and shifts in vegetation composition toward less palatable species, may confound predicted responses to changes in productivity in higher ANPP communities such as the MAT studied here.

A shared MHC supertype motif emerges by convergent evolution in macaques and mice, but is totally absent in human MHC molecules - Alessandro Sette; John Sidney; Scott Southwood; Carrie Moore; Jessica Berry; Courtney Dow; Kate Bradley; Ilka Hoof; Mark G. Lewis; William H. Hildebrand; Curtis P. McMurtrey; Nancy A. Wilson; et al. (Immunogenetics, 2012)

Decision support system for forest fire protection in the Euro-Mediterranean region - Kostas Kalabokidis; Gavriil Xanthopoulos; Peter Moore; David Caballero; George Kallos; Juan Llorens; Olga Roussou; Christos Vasilakos (European Journal of Forest Research, 2012)

Total ozone and surface UV trends in the United Kingdom: 1979–2008 - Andrew R. D. Smedley; John S. Rimmer; David Moore; Ralf Toumi; Ann R. Webb (International Journal of Climatology, 2012)
In this study we present the UK's total ozone and UV data records, their measurement and preliminary processing, and discuss the observed trends. Notably, we combine the records from the Camborne and Reading sites to obtain a single ozone data series for southern England—a total duration of 30 years. Two‐section linear trends and cross‐over years are determined for Lerwick and southern England, both annually and seasonally. The observed minimum using this technique in the UK ozone record is found to occur during the year 1993. Significant trends of − 4.8% per decade for southern England and − 5.8% per decade for Lerwick are seen prior to the mid‐1990s; the rate of decrease in the UK being at the upper limit of other European stations. No significant ozone trend is seen for the latter period in either location in contrast with Europe as a whole. We, additionally, compare the satellite‐derived total ozone trends for both locations. The UV record at Reading showed a significant trend from 1993 to 2008 in the daily maximum UV index record (6.6% per decade), despite no significant recovery in the total ozone data series, suggesting a reduction in cloud cover during the midday period. Filtering data to remove other factors shows the erythemal UV to have an ozone‐dependent trend of − 0.11% per year, but this is not statistically significant. We find no correlation between anomalies in the surface UV and total ozone records suggesting that the majority of the inter‐annual variability is due to changes in cloud cover and other effects. Copyright © 2011 Royal Meteorological Society

Influences of Salinity and Light Availability on Abundance and Distribution of Tidal Freshwater and Oligohaline Submersed Aquatic Vegetation - Erin C. Shields; Kenneth A. Moore; David B. Parrish (Estuaries and Coasts, 2012)

The structure and functioning of the couplon in the mammalian cardiomyocyte - Parisa Asghari; David R. L. Scriven; Jeremy Hoskins; Nicola Fameli; Cornelis van Breemen; Edwin D. W. Moore (Protoplasma, 2012)

Effects of biotic disturbances on forest carbon cycling in the U nited S tates and C anada - Jeffrey A. Hicke; Craig D. Allen; Ankur R. Desai; Michael C. Dietze; Ronald J. Hall; Edward H. (Ted) Hogg; Daniel M. Kashian; David Moore; Kenneth F. Raffa; Rona N. Sturrock; James Vogelmann (Global Change Biology, 2012)
Forest insects and pathogens are major disturbance agents that have affected millions of hectares in N orth A merica in recent decades, implying significant impacts to the carbon ( C ) cycle. Here, we review and synthesize published studies of the effects of biotic disturbances on forest C cycling in the U nited S tates and C anada. Primary productivity in stands was reduced, sometimes considerably, immediately following insect or pathogen attack. After repeated growth reductions caused by some insects or pathogens or a single infestation by some bark beetle species, tree mortality occurred, altering productivity and decomposition. In the years following disturbance, primary productivity in some cases increased rapidly as a result of enhanced growth by surviving vegetation, and in other cases increased slowly because of lower forest regrowth. In the decades following tree mortality, decomposition increased as a result of the large amount of dead organic matter. Net ecosystem productivity decreased immediately following attack, with some studies reporting a switch to a C source to the atmosphere, and increased afterward as the forest regrew and dead organic matter decomposed. Large variability in C cycle responses arose from several factors, including type of insect or pathogen, time since disturbance, number of trees affected, and capacity of remaining vegetation to increase growth rates following outbreak. We identified significant knowledge gaps, including limited understanding of carbon cycle impacts among different biotic disturbance types (particularly pathogens), their impacts at landscape and regional scales, and limited capacity to predict disturbance events and their consequences for carbon cycling. We conclude that biotic disturbances can have major impacts on forest C stocks and fluxes and can be large enough to affect regional C cycling. However, additional research is needed to reduce the uncertainties associated with quantifying biotic disturbance effects on the N orth A merican C budget.

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Quantitative approaches in climate change ecology - Christopher J. Brown; David S. Schoeman; William J. Sydeman; Keith Brander; Lauren B. Buckley; Michael Burrows; Carlos M. Duarte; Pippa J. Moore; John M. Pandolfi; Elvira Poloczanska; William Venables; Anthony J. Richardson (Global Change Biology, 2011)
Contemporary impacts of anthropogenic climate change on ecosystems are increasingly being recognized. Documenting the extent of these impacts requires quantitative tools for analyses of ecological observations to distinguish climate impacts in noisy data and to understand interactions between climate variability and other drivers of change. To assist the development of reliable statistical approaches, we review the marine climate change literature and provide suggestions for quantitative approaches in climate change ecology. We compiled 267 peer‐reviewed articles that examined relationships between climate change and marine ecological variables. Of the articles with time series data ( n = 186), 75% used statistics to test for a dependency of ecological variables on climate variables. We identified several common weaknesses in statistical approaches, including marginalizing other important non‐climate drivers of change, ignoring temporal and spatial autocorrelation, averaging across spatial patterns and not reporting key metrics. We provide a list of issues that need to be addressed to make inferences more defensible, including the consideration of (i) data limitations and the comparability of data sets; (ii) alternative mechanisms for change; (iii) appropriate response variables; (iv) a suitable model for the process under study; (v) temporal autocorrelation; (vi) spatial autocorrelation and patterns; and (vii) the reporting of rates of change. While the focus of our review was marine studies, these suggestions are equally applicable to terrestrial studies. Consideration of these suggestions will help advance global knowledge of climate impacts and understanding of the processes driving ecological change.

Manganese sulfide formation via concomitant microbial manganese oxide and thiosulfate reduction - Ji‐Hoon Lee; David W. Kennedy; Alice Dohnalkova; Dean A. Moore; Ponnusamy Nachimuthu; Samantha B. Reed; James K. Fredrickson (Environmental Microbiology, 2011)
Summary The dissimilatory metal‐reducing bacterium, Shewanella oneidensis MR‐1 produced γ‐MnS (rambergite) nanoparticles during the concurrent reduction of MnO 2 and thiosulfate coupled to H 2 oxidation. To investigate effect of direct microbial reduction of MnO 2 on MnS formation, two MR‐1 mutants defective in outer membrane c ‐type cytochromes (Δ mtrC /Δ omcA and Δ mtrC /Δ omcA /Δ mtrF ) were also used and it was determined that direct reduction of MnO 2 was dominant relative to chemical reduction by biogenic sulfide generated from thiosulfate reduction. Although bicarbonate was excluded from the medium, incubations of strain MR‐1 with lactate as the electron donor produced MnCO 3 (rhodochrosite) as well as MnS in nearly equivalent amounts as estimated by micro X‐ray diffraction (micro‐XRD) analysis. It was concluded that carbonate released from lactate metabolism promoted MnCO 3 formation and that Mn(II) mineralogy was strongly affected by carbonate ions even in the presence of abundant sulfide and weakly alkaline conditions expected to favour the precipitation of MnS. Formation of MnS, as determined by a combination of micro‐XRD, transmission electron microscopy, energy dispersive X‐ray spectroscopy, and selected area electron diffraction analyses was consistent with equilibrium speciation modelling predictions. Biogenic manganese sulfide may be a manganese sink in the Mn biogeochemical cycle in select environments such as deep anoxic marine basins within the Baltic Sea.

Current concentrations and spatial and temporal trends in mercury in Great Lakes Herring Gull eggs, 1974–2009 - D. V. Chip Weseloh; David J. Moore; Craig E. Hebert; Shane R. de Solla; Birgit M. Braune; Daryl J. McGoldrick (Ecotoxicology, 2011)

Water-Use Dynamics of an Invasive Reed, Arundo donax, from Leaf to Stand - David A. Watts; Georgianne W. Moore (Wetlands, 2011)

Synthesis and characterization of an unsymmetrical cobalt(III) active site analogue of nitrile hydratase - Jennifer K. Angelosante; Lauren M. Schopp; Breia J. Lewis; Amber D. Vitalo; Dustin T. Titus; Rebecca A. Swanson; April N. Stanley; Brendan P. Abolins; Michelle J. Frome; Lisa E. Cooper; David L. Tierney; Curtis Moore; et al. (JBIC Journal of Biological Inorganic Chemistry, 2011)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 1. Overview and Problem Formulation - Donald D. MacDonald; Dwayne R. J. Moore; Christopher G. Ingersoll; Dawn E. Smorong; R. Scott Carr; Ron Gouguet; David Charters; Duane Wilson; Tom Harris; Jon Rauscher; Susan Roddy; John Meyer (Archives of Environmental Contamination and Toxicology, 2011)

Genes in the insulin and insulin-like growth factor pathway and odds of metachronous colorectal neoplasia - Elizabeth C. LeRoy; Jason H. Moore; Chengcheng Hu; María Elena Martínez; Peter Lance; David Duggan; Patricia A. Thompson (Human Genetics, 2011)

Contribution of inter-subunit interactions to the thermostability of Pyrococcus furiosus citrate synthase - Vicky Moore; Ami Kanu; Olwyn Byron; Gordon Campbell; Michael J. Danson; David W. Hough; Susan J. Crennell (Extremophiles, 2011)

Mapping Soil Pore Water Salinity of Tidal Marsh Habitats Using Electromagnetic Induction in Great Bay Estuary, USA - Gregg E. Moore; David M. Burdick; Chris R. Peter; Donald R. Keirstead (Wetlands, 2011)

Current and future treatment options in osteoporosis - Linda Brewer; David Williams; Alan Moore (European Journal of Clinical Pharmacology, 2011)

Neurocognitive functioning in acute or early HIV infection - David J. Moore; Scott L. Letendre; Sheldon Morris; Anya Umlauf; Reena Deutsch; Davey M. Smith; Susan Little; Alexandra Rooney; Donald R. Franklin; Ben Gouaux; Shannon LeBlanc; Debra Rosario; et al. (Journal of NeuroVirology, 2011)

Successful cognitive aging in persons living with HIV infection - Lauren Malaspina; Steven Paul Woods; David J. Moore; Colin Depp; Scott L. Letendre; Dilip Jeste; Igor Grant (Journal of NeuroVirology, 2011)

Age-related changes in the corpus callosum in early-onset bipolar disorder assessed using volumetric and cross-sectional measurements - Melissa Lopez-Larson; Janis L. Breeze; David N. Kennedy; Steven M. Hodge; Lena Tang; Constance Moore; Anthony J. Giuliano; Nikos Makris; Verne S. Caviness; Jean A. Frazier (Brain Imaging and Behavior, 2010)

Estimating parameters of a forest ecosystem C model with measurements of stocks and fluxes as joint constraints - Andrew D. Richardson; Mathew Williams; David Y. Hollinger; David J. P. Moore; D. Bryan Dail; Eric A. Davidson; Neal A. Scott; Robert S. Evans; Holly Hughes; John T. Lee; Charles Rodrigues; Kathleen Savage (Oecologia, 2010)

Long-Term Trends in Submersed Aquatic Vegetation (SAV) in Chesapeake Bay, USA, Related to Water Quality - Robert J. Orth; Michael R. Williams; Scott R. Marion; David J. Wilcox; Tim J. B. Carruthers; Kenneth A. Moore; W. Michael Kemp; William C. Dennison; Nancy Rybicki; Peter Bergstrom; Richard A. Batiuk (Estuaries and Coasts, 2010)

A first look at the effects of ionospheric signal bending on a globally processed GPS network - Elizabeth J. Petrie; Matt A. King; Philip Moore; David A. Lavallée (Journal of Geodesy, 2010)

Longer growing seasons lead to less carbon sequestration by a subalpine forest - JIA HU; DAVID J. P. MOORE; SEAN P. BURNS; RUSSELL K. MONSON (Global Change Biology, 2010)
As global temperatures increase, the potential for longer growing seasons to enhance the terrestrial carbon sink has been proposed as a mechanism to reduce the rate of further warming. At the Niwot Ridge AmeriFlux site, a subalpine forest in the Colorado Rocky Mountains, we used a 9‐year record (1999–2007) of continuous eddy flux observations to show that longer growing season length (GSL) actually resulted in less annual CO 2 uptake. Years with a longer GSL were correlated with a shallower snow pack, as measured using snow water equivalent (SWE). Furthermore, years with a lower SWE correlated with an earlier start of spring. For three years, 2005, 2006, and 2007, we used observations of stable hydrogen isotopes ( δ D) of snow vs. rain, and extracted xylem water from the three dominant tree species, lodgepole pine, Engelmann spruce, and subalpine fir, to show that the trees relied heavily on snow melt water even late into the growing season. By mid‐August, 57% to 68% of xylem water reflected the isotopic signature of snow melt. By coupling the isotopic water measurements with an ecosystem model, SIPNET, we found that annual forest carbon uptake was highly dependent on snow water, which decreases in abundance during years with longer growing seasons. Once again, for the 3 years 2005, 2006, and 2007, annual gross primary productivity, which was derived as an optimized parameter from the SIPNET model was estimated to be 67% 77%, and 71% dependent on snow melt water, respectively. Past studies have shown that the mean winter snow pack in mountain ecosystems of the Western US has been declining for decades and is correlated with positive winter temperature anomalies. Since climate change models predict continuation of winter warming and reduced snow in mountains of the Western US, the strength of the forest carbon sink is likely to decline further.

Eelgrass (Zostera marina L.) in the Chesapeake Bay Region of Mid-Atlantic Coast of the USA: Challenges in Conservation and Restoration - Robert J. Orth; Scott R. Marion; Kenneth A. Moore; David J. Wilcox (Estuaries and Coasts, 2010)

Alterations in peroxisome proliferator-activated receptor mRNA expression in skeletal muscle after acute and repeated bouts of exercise - Espen E. Spangenburg; David A. Brown; Micah S. Johnson; Russell L. Moore (Molecular and Cellular Biochemistry, 2009)

Clearance and Phosphorylation of Alpha-Synuclein Are Inhibited in Methionine Sulfoxide Reductase A Null Yeast Cells - Derek B. Oien; Heather E. Shinogle; David S. Moore; Jackob Moskovitz (Journal of Molecular Neuroscience, 2009)

Geometry of the Nojima Fault at Nojima-Hirabayashi, Japan – II. Microstructures and their Implications for Permeability and Strength - Diane E. Moore; David A. Lockner; Hisao Ito; Riuji Ikeda; Hidemi Tanaka; Kentaro Omura (Pure and Applied Geophysics, 2009)

Soil solution and sugar maple response to NH4NO3 additions in a base-poor northern hardwood forest of Québec, Canada - Jean-David Moore; Daniel Houle (Environmental Monitoring and Assessment, 2009)

Socioeconomic status in relation to early menarche among black and white girls - Dejana Braithwaite; Dan H. Moore; Robert H. Lustig; Elissa S. Epel; Ken K. Ong; David H. Rehkopf; May C. Wang; Suzanne M. Miller; Robert A. Hiatt (Cancer Causes & Control, 2009)

Cognitive Neuropsychology of HIV-Associated Neurocognitive Disorders - Steven Paul Woods; David J. Moore; Erica Weber; Igor Grant (Neuropsychology Review, 2009)

A Rapid Method to Score Stream Reaches Based on the Overall Performance of Their Main Ecological Functions - David K. Rowe; Stephanie Parkyn; John Quinn; Kevin Collier; Chris Hatton; Michael K. Joy; John Maxted; Stephen Moore (Environmental Management, 2009)

Differential Contributions of Lateral Prefrontal Cortex Regions to Visual Memory Processes - Nicole C. R. McLaughlin; Dana W. Moore; Carl Fulwiler; Rafeeque Bhadelia; David A. Gansler (Brain Imaging and Behavior, 2009)

The NOPP O-SCOPE and MOSEAN Projects: Advanced Sensing for Ocean Observing Systems - Tommy Dickey; Nick Bates; Robert Byrne; Grace Chang; Francisco Chavez; Richard Feely; Alfred Hanson; David Karl; Derek Manov; Casey Moore; Christopher Sabine; Rik Wanninkhof (Oceanography, 2009)

Cost‐Effective Management of Snake River Chinook Salmon: Response to Wilson et al. - DAVID L. HALSING; MICHAEL R. MOORE (Conservation Biology, 2009)

Diversity in Current Ecological Thinking: Implications for Environmental Management - Susan A. Moore; Tabatha J. Wallington; Richard J. Hobbs; Paul R. Ehrlich; C. S. Holling; Simon Levin; David Lindenmayer; Claudia Pahl-Wostl; Hugh Possingham; Monica G. Turner; Mark Westoby (Environmental Management, 2009)

Increased frequency of α-synuclein in the substantia nigra in human immunodeficiency virus infection - Negar Khanlou; Negar Khanlou; David J Moore; Negar Khanlou; David J Moore; Gursharan Chana; Mariana Cherner; Deborah Lazzaretto; Sharron Dawes; Igor Grant; Eliezer Masliah; Ian P Everall; et al. (Journal of NeuroVirology, 2009)

Monophyly of terrestrial adephagan beetles as indicated by three nuclear genes (Coleoptera: Carabidae and Trachypachidae) - David R. Maddison; Wendy Moore; Michael D. Baker; Tana M. Ellis; Karen A. Ober; Jamie J Cannone; Robin R. Gutell (Zoologica Scripta, 2009)
The beetle suborder Adephaga is traditionally divided into two sections on the basis of habitat, terrestrial Geadephaga and aquatic Hydradephaga. Monophyly of both groups is uncertain, and the relationship of the two groups has implications for inferring habitat transitions within Adephaga. Here we examine phylogenetic relationships of these groups using evidence provided by DNA sequences from all four suborders of beetles, including 60 species of Adephaga, 4 Archostemata, 3 Myxophaga, and 10 Polyphaga. We studied 18S ribosomal DNA and 28S ribosomal DNA, aligned with consideration of secondary structure, as well as the nuclear protein‐coding gene wingless . Independent and combined Bayesian, likelihood, and parsimony analyses of all three genes supported placement of Trachypachidae in a monophyletic Geadephaga, although for analyses of 28S rDNA and some parsimony analyses only if Coleoptera is constrained to be monophyletic. Most analyses showed limited support for the monophyly of Hydradephaga. Outside of Adephaga, there is support from the ribosomal genes for a sister group relationship between Adephaga and Polyphaga. Within the small number of sampled Polyphaga, analyses of 18S rDNA, wingless , and the combined matrix supports monophyly of Polyphaga exclusive of Scirtoidea. Unconstrained analyses of the evolution of habitat suggest that Adephaga was ancestrally aquatic with one transition to terrestrial. However, in analyses constrained to disallow changes from aquatic to terrestrial habitat, the phylogenies imply two origins of aquatic habit within Adephaga.

The effect of carbon dioxide enrichment on apparent stem respiration from Pinus taeda L. is confounded by high levels of soil carbon dioxide - David J. P. Moore; Miquel A. Gonzalez-Meler; Lina Taneva; Jeffrey S. Pippen; Hyun-Seok Kim; Evan H. DeLucia (Oecologia, 2008)

COMPARATIVE ECOLOGY OF NORTH ATLANTIC SHORES: DO DIFFERENCES IN PLAYERS MATTER FOR PROCESS? - Stuart R. Jenkins; Pippa Moore; Michael T. Burrows; David J. Garbary; Stephen J. Hawkins; Agnar Ingólfsson; Kenneth P. Sebens; Paul V. R. Snelgrove; David S. Wethey; Sarah A. Woodin (Ecology, 2008)
The contrasting histories of the western and eastern shores of the North Atlantic Ocean provide an excellent opportunity to consider the implications of past events for present ecological processes and the functioning of marine ecosystems. Similarities and differences in assemblage composition have been driven by large‐scale events, such as the trans‐Arctic interchange, which has shaped the species pool, and cycles of glaciation, which have determined phases of local or regional extinction and colonization. More recently, anthropogenically induced invasions and local extinctions have significantly altered biogeographic distributions. Here we consider for both hard and soft substrata how the presence or absence of key taxa influences the outcomes of trophic and other biological interactions, and evaluate the consequences for community structure and ecosystem functioning. On intertidal hard substratum shores, biodiversity of epilithic microphagous grazers differs across latitudinal and longitudinal scales. Diversity is high in southern Europe but declines to the north and across the Atlantic. Lower diversity and the absence of patellid limpets in Iceland and the northwest Atlantic compared to Europe result in differences in consumer pressure, and an apparent contrast in the importance of herbivory vs. competitive interactions and predation pressure as community structuring processes. Interestingly, despite differences in “process,” community patterns are remarkably similar between the east and west. On soft sediment shores, there are conspicuous geographic differences in importance of bioturbators and large digging predators. Hemichordates can be abundant and important infaunal bioturbators in the western Atlantic, but they generally play a much reduced role in the eastern Atlantic. In addition, the number and diversity of digging predators on western Atlantic shores is high; the horseshoe crab, swimming portunid crabs, large whelks, excavating waterfowl, and an abundance of skates and rays exert intense predation pressure and associated biogenic disturbance to sediments. In Europe, except for excavating waterfowl these taxa are rare or absent. Thus, the importance of large, biological agents of disturbance is lower on European shores as a consequence of both recent anthropogenic pressure and natural processes over larger time scales. Consideration of key structuring taxa over the Atlantic shows that human‐mediated transport has had considerable influence. Faunas on both sides of the Atlantic are becoming more similar to the point that some of the key differences in assemblage composition and hence community organization have blurred. Recent introductions as well as planned experimental manipulations provide the opportunity to understand the role of species identity in determining community structure and ecosystem functioning over large spatial scales; the North Atlantic may be an ideal test system to explore these areas.

Production of Dissolved Organic Carbon in Canadian Forest Soils - Tim R. Moore; David Paré; Robert Boutin (Ecosystems, 2008)

Does context influence the duration of locomotor sensitization to ethanol in female DBA/2J mice? - Stephen L. Boehm; Karen J. Goldfarb; Kristen M. Serio; Eileen M. Moore; David N. Linsenbardt (Psychopharmacology, 2008)

Cost‐Effective Management Alternatives for Snake River Chinook Salmon: a Biological‐Economic Synthesis - DAVID L. HALSING; MICHAEL R. MOORE (Conservation Biology, 2008)
The mandate to increase endangered salmon populations in the Columbia River Basin of North America has created a complex, controversial resource‐management issue. We constructed an integrated assessment model as a tool for analyzing biological‐economic trade‐offs in recovery of Snake River spring‐ and summer‐run chinook salmon ( Oncorhynchus tshawytscha ). We merged 3 frameworks: a salmon‐passage model to predict migration and survival of smolts; an age‐structured matrix model to predict long‐term population growth rates of salmon stocks; and a cost‐effectiveness analysis to determine a set of least‐cost management alternatives for achieving particular population growth rates. We assessed 6 individual salmon‐management measures and 76 management alternatives composed of one or more measures. To reflect uncertainty, results were derived for different assumptions of effectiveness of smolt transport around dams. Removal of an estuarine predator, the Caspian Tern ( Sterna caspia ), was cost‐effective and generally increased long‐term population growth rates regardless of transport effectiveness. Elimination of adult salmon harvest had a similar effect over a range of its cost estimates. The specific management alternatives in the cost‐effective set depended on assumptions about transport effectiveness. On the basis of recent estimates of smolt transport effectiveness, alternatives that discontinued transportation or breached dams were prevalent in the cost‐effective set, whereas alternatives that maximized transportation dominated if transport effectiveness was relatively high. More generally, the analysis eliminated 80–90% of management alternatives from the cost‐effective set. Application of our results to salmon management is limited by data availability and model assumptions, but these limitations can help guide research that addresses critical uncertainties and information. Our results thus demonstrate that linking biology and economics through integrated models can provide valuable tools for science‐based policy and management.

Aboveground net primary production dynamics in a northern Chihuahuan Desert ecosystem - Esteban H. Muldavin; Douglas I. Moore; Scott L. Collins; Karen R. Wetherill; David C. Lightfoot (Oecologia, 2008)

An Overview of Fixed Passive Acoustic Observation Methods for Cetaceans - David Mellinger; Kathleen Stafford; Sue Moore; Robert Dziak; Haru Matsumoto (Oceanography, 2007)

Efficacy of Vegetated Buffers in Preventing Transport of Fecal Coliform Bacteria from Pasturelands - Timothy J. Sullivan; James A. Moore; David R. Thomas; Eric Mallery; Kai U. Snyder; Mark Wustenberg; Judith Wustenberg; Sam D. Mackey; Deian L. Moore (Environmental Management, 2007)

A substance flow analysis in the southern hemisphere: cadmium in the Australian economy - Suphaphat Kwonpongsagoon; David T. Waite; Stephen J. Moore; Paul H. Brunner (Clean Technologies and Environmental Policy, 2007)

Effect of adenoviral mediated overexpression of fibromodulin on human dermal fibroblasts and scar formation in full-thickness incisional wounds - Alexander Stoff; Angel A. Rivera; J. Michael Mathis; Steven T. Moore; N. S. Banerjee; Maaike Everts; Antonio Espinosa-de-los-Monteros; Zdenek Novak; Luis O. Vasconez; Thomas R. Broker; Dirk F. Richter; Dale Feldman; et al. (Journal of Molecular Medicine, 2007)

Unobtrusive integration of data management with fMRI analysis - Andrew V. Poliakov; Xenia Hertzenberg; Eider B. Moore; David P. Corina; George A. Ojemann; James F. Brinkley (Neuroinformatics, 2007)

Image Correlation Algorithm for Measuring Lymphocyte Velocity and Diameter Changes in Contracting Microlymphatics - J. Brandon Dixon; Anatoliy A. Gashev; David C. Zawieja; James E. Moore; Gerard L. Coté (Annals of Biomedical Engineering, 2007)

Annual basal area increment and growth duration of Pinus taeda in response to eight years of free‐air carbon dioxide enrichment - DAVID J. P. MOORE; SUSANNE AREF; RINGO M. HO; JEFFREY S. PIPPEN; JASON G. HAMILTON; EVAN H. DE LUCIA (Global Change Biology, 2006)
Rising CO 2 is predicted to increase forest productivity, although the duration of the response and how it might be altered by variation in rainfall, temperature and other environmental variables are not well understood. We measured the basal area of rapidly growing Pinus taeda trees exposed to free‐air CO 2 enrichment for 8 years and used these measurements to estimate monthly and annual growth. We used these measurements in a statistical model to estimate the start and end of growth in each year. Elevated CO 2 increased the basal area increment ( BAI ) of trees by 13–27%. In most years, exposure to elevated CO 2 increased the growth rate but not the duration of the active growth period. With the exception of 1 year following an extreme drought and a severe ice storm, BAI was positively correlated with the amount of rainfall during the active growth period. The interannual variation in the relative enhancement of BAI caused by elevated CO 2 was strongly related to temperature and rainfall, and was greatest in years with high vapor pressure deficit. There was no evidence of a systematic reduction in the stimulation of growth during the first 8 years of this experiment, suggesting that the hypothesized limitation of the CO 2 response caused by nitrogen availability has yet to occur.

Marble-hosted sulfide ores in the Angouran Zn-(Pb–Ag) deposit, NW Iran: interaction of sedimentary brines with a metamorphic core complex - H. Albert Gilg; Maria Boni; Giuseppina Balassone; Cameron R. Allen; David Banks; Farid Moore (Mineralium Deposita, 2006)

Physiological state of phytoplankton communities in the Southwest Atlantic sector of the Southern Ocean, as measured by fast repetition rate fluorometry - Claire L. Holeton; Florence Nédélec; Richard Sanders; Louise Brown; C. Mark Moore; David P. Stevens; Karen J. Heywood; Peter J. Statham; Cathy H. Lucas (Polar Biology, 2005)

Exploring the Relationship Between Hydrologic Parameters and Nutrient Loads Using Digital Elevation Model and GIS – A Case Study from Sugarcreek Headwaters, Ohio, U.S.A. - V. Krishna Prasad; Ariel Ortiz; Ben Stinner; David Mccartney; Jason Parker; Deana Hudgins; Casey Hoy; Richard Moore (Environmental Monitoring and Assessment, 2005)

Lack of effects of guanfacine on executive and memory functions in healthy male volunteers - Ulrich Müller; Luke Clark; Minh L. Lam; Rebecca M. Moore; C. Louise Murphy; Nicola K. Richmond; Ranbir S. Sandhu; Ingrid A. Wilkins; David K. Menon; Barbara J. Sahakian; Trevor W. Robbins (Psychopharmacology, 2005)

Wood properties of juvenile Pinus radiata growing in the presence and absence of competing understorey vegetation at a dryland site - Michael S. Watt; Geoffrey M. Downes; David Whitehead; Euan G. Mason; Brian Richardson; Jenny C. Grace; John R. Moore (Trees, 2005)

DETECTION OF NORTH PACIFIC RIGHT WHALE ( EUBALAENA JAPONICA ) CALLS IN THE GULF OF ALASKA - David K. Mellinger; Kathleen M. Stafford; Sue E. Moore; Lisa Munger; Christopher G. Fox (Marine Mammal Science, 2004)

Induced defences in an endangered amphibian in response to an introduced snake predator - Robin D. Moore; Richard A. Griffiths; Cliona M. O’Brien; Adam Murphy; David Jay (Oecologia, 2004)

Detritus, trophic dynamics and biodiversity - John C. Moore; Eric L. Berlow; David C. Coleman; Peter C. de Ruiter; Quan Dong; Alan Hastings; Nancy Collins Johnson; Kevin S. McCann; Kim Melville; Peter J. Morin; Knute Nadelhoffer; Amy D. Rosemond; et al. (Ecology Letters, 2004)
Traditional approaches to the study of food webs emphasize the transfer of local primary productivity in the form of living plant organic matter across trophic levels. However, dead organic matter, or detritus, a common feature of most ecosystems plays a frequently overlooked role as a dynamic heterogeneous resource and habitat for many species. We develop an integrative framework for understanding the impact of detritus that emphasizes the ontogeny and heterogeneity of detritus and the various ways that explicit inclusion of detrital dynamics alters generalizations about the structure and functioning of food webs. Through its influences on food web composition and dynamics, detritus often increases system stability and persistence, having substantial effects on trophic structure and biodiversity. Inclusion of detrital heterogeneity in models of food web dynamics is an essential new direction for ecological research.

Species distributions, surrogacy, and important conservation regions in Canada - Leanna D. Warman; David M. Forsyth; A. R. E. Sinclair; Kathryn Freemark; Harold D. Moore; Thomas W. Barrett; R. L. Pressey; Denis White (Ecology Letters, 2004)
Conservation actions could be more efficient if there is congruence among taxa in the distribution of species. Patterns in the geographical distribution of five taxa were used to identify nationally important regions for conservation in Canada. Two measures of surrogacy were significantly and positively correlated among taxa, and conservation areas selected for one taxon represented other taxa significantly better than random selections. However, few large protected areas exist in the sites of highest conservation value in southern Canada; these regions are therefore a priority for future conservation regard. By focusing this effort on threatened and endangered species, which are a national priority in Canada, most other species could also benefit.

Comparison of Historical and Contemporary Forest Structure and Composition on Permanent Plots in Southwestern Ponderosa Pine Forests - Margaret M. Moore; David W. Huffman; Peter Z. Fulé; W. Wallace Covington; Joseph E. Crouse (Forest Science, 2004)
We compared historical (1909–1913) and contemporary (1997–1999) forest structure and composition on 15 permanent plots in ponderosa pine (Pinus ponderosa Dougl. ex Laws.) forests of Arizona and New Mexico. We used the same sampling methods as in the early 1900s and compared stand density, diameter distributions, species composition, and broad age classes from the two periods. Stand density (trees ≥9.14 cm dbh) significantly (P < 0.001) increased on plots from an average of 77.4 trees per plot (s = 49.9) at plot establishment in 1909–1913 to 519.1 trees per plot (s = 252.3) at remeasurement in 1997–1999. Basal area significantly (P < 0.001) increased from 8.0 m2 per plot (s = 3.5) to 28.5 m2 per plot (s = 10.1). Contemporary tree diameter distribution shifted toward smaller size classes as demonstrated by a significant (P = 0.001) decrease in quadratic mean diameter from 38.5 cm (s = 7.5) in 1909–1913 to 28.6 cm (s = 7.1) in 1997–1999. Broad age classes yielded an average of 61.5 (s = 49.5) residual live trees classified as “blackjack” ponderosa pine (P. ponderosa <150 years) and 13.3 (s = 11.9) “yellow pine” (P. ponderosa ≥150 years) in 1909–1913. In 1997–1999, 416 live trees (s = 229.6) were “blackjack” and 57.2 (s = 28.5) trees on average were “yellow pine.” Twelve of the 15 plots were not invaded by other tree species (remained pure ponderosa pine type), while composition shifted slightly on three plots toward more shade-tolerant and fire-intolerant species. Ninety-one percent of the historically (1909–1913 or older) mapped tree structures (live trees, snags, logs, stumps, etc.) were relocated, which suggested that the forest reconstruction field techniques are reliable within 10%. Dramatic increases in tree densities may represent an increased potential for bark beetle epidemics and stand replacing wildfire over large areas in the Southwest. FOR. SCI. 50(2):162–176.

Mycorrhizal promotion of host stomatal conductance in relation to irradiance and temperature - Keunho Cho; Robert M. Aug; Jennifer L. Moore; David M. Sylvia (Mycorrhiza, 2004)

Climatic Suitability, Life‐History Traits, Introduction Effort, and the Establishment and Spread of Introduced Mammals in Australia - DAVID M. FORSYTH; RICHARD P. DUNCAN; MARY BOMFORD; GEOFF MOORE (Conservation Biology, 2004)
Major progress in understanding biological invasions has recently been made by quantitatively comparing successful and unsuccessful invasions. We used such an approach to test hypotheses about the role of climatic suitability, life history, and historical factors in the establishment and subsequent spread of 40 species of mammal that have been introduced to mainland Australia. Relative to failed species, the 23 species that became established had a greater area of climatically suitable habitat available in Australia, had previously become established elsewhere, had a larger overseas range, and were introduced more times. These relationships held after phylogeny was controlled for, but successful species were also significantly more likely to be nonmigratory. A forward‐selection model included only two of the nine variables for which we had data for all species: climatic suitability and introduction effort. When the model was adjusted for phylogeny, those same two variables were included, along with previous establishment success. Of the established species, those with a larger geographic range size in Australia had a greater area of climatically suitable habitat, had traits associated with a faster population growth rate (small body size, shorter life span, lower weaning age, more offspring per year), were nonherbivorous, and had a larger overseas range size. When the model was adjusted for phylogeny, the importance of climatic suitability and the life‐history traits remained significant, but overseas range size was no longer important and species with greater introduction effort had a larger geographic range size. Two variables explained variation in geographic range size in a forward‐selection model: species with smaller body mass and greater longevity tended to have larger range sizes in Australia. These results mirror those from a recent analysis of exotic‐bird introductions into Australia, suggesting that, at least among vertebrate taxa, similar factors predict establishment and spread. Our approach and results are being used to assess the risks of exotic vertebrates becoming established and spreading in Australia.

Does the myosin V neck region act as a lever? - Jeffrey R. Moore; Elena B. Krementsova; Kathleen M. Trybus; David M. Warshaw (Journal of Muscle Research and Cell Motility, 2004)

Imprinted methylation profiles for proximal mouse Chromosomes 11 and 7 as revealed by methylation-sensitive representational difference analysis - Jo Peters; Gavin Kelsey; Gudrun E. Moore; Rachel Smith; Philippe Arnaud; Michael A. Preece; David Monk; Philip Stanier; Colin V. Beechey (Mammalian Genome, 2003)

Place Attachment and Context: Comparing a Park and a Trail Within - Roger L. Moore; David Scott (Forest Science, 2003)
A number of recent studies have focused on place attachment, defined as the extent to which a person values or identifies with a particular setting. Some studies suggest that place attachment includes an emotional/symbolic “place identity” dimension and a functional “place dependence” dimension. One aspect of place attachment that has not been explored empirically is the extent to which people become attached to a specific site versus its larger setting. The main purpose of this study was to examine users' place attachment to a large metropolitan park versus their place attachment to a particular trail located within that same park. The study sample was comprised of 438 recreational users of a paved trail located in a large regional park near Cleveland, Ohio. Major findings include: (1) Frequency of use was positively related to both park and trail attachment. (2) Levels of trail attachment varied across different trail activities, but levels of park attachment did not. (3) The most powerful predictor of both park attachment and trail attachment was personal commitment to the activity that users were pursuing. (4) –Unlike previous research, factor analyses indicated that both park and trail attachment were unidimensional rather than comprised of place identity and dependence dimensions. Implications for management and research are discussed.

Potential triggers for akinete differentiation in an Australian strain of the cyanobacterium Cylindrospermopsis raciborskii (AWT 205/1) - David Moore; Mark O'Donohue; Glen Shaw; Christa Critchley (Hydrobiologia, 2003)

Sequence variation in the CHAT locus shows no association with late-onset Alzheimer's disease - Denise Harold; Timothy Peirce; Valentina Moskvina; Simon Lovestone; John Powell; Catherine Foy; Nicola Archer; Sarah Walter; Amanda Edmonson; Stephen McIlroy; David Craig; Peter A. Passmore; et al. (Human Genetics, 2003)

Biogeochemical transformations of arsenic in circumneutral freshwater sediments - David R. Nicholas; Srividhya Ramamoorthy; Vince Palace; Stefan Spring; Johnnie N. Moore; R. Frank Rosenzweig (Biodegradation, 2003)

Stratigraphy of the mid-Holocene black bands in Lakes Michigan and Huron: Evidence for possible basin-wide anoxia - Carrie Odegaard; David K. Rea; Theodore C. Moore (Journal of Paleolimnology, 2003)

DDC and COBL, flanking the imprinted GRB10 gene on 7p12, are biallelically expressed - Megan P. Hitchins; Louise Bentley; David Monk; Colin Beechey; Jo Peters; Gavin Kelsey; Fumitoshi Ishino; Michael A. Preece; Philip Stanier; Gudrun E. Moore (Mammalian Genome, 2002)

Chromosome 7p disruptions in Silver Russell syndrome: delineating an imprinted candidate gene region. - David Monk; Louise Bentley; Megan Hitchins; Rachael Myler; Jill Clayton-Smith; Samira Ismail; Sue Price; Michael Preece; Philip Stanier; Gudrun Moore (Human Genetics, 2002)

Distribution of Metals in Water and Bed Sediment in a Mineral-Rich Watershed, Montana, USA - Sonia A. Nagorski; Johnnie N. Moore; David B. Smith (Mine Water and the Environment, 2002)

A meta‐analysis of elevated [CO 2 ] effects on soybean ( Glycine max ) physiology, growth and yield - Elizabeth A. Ainsworth; Phillip A. Davey; Carl J. Bernacchi; Orla C. Dermody; Emily A. Heaton; David J. Moore; Patrick B. Morgan; Shawna L. Naidu; Hyung‐shim Yoo Ra; Xin‐guang Zhu; Peter S. Curtis; Stephen P. Long (Global Change Biology, 2002)
The effects of elevated [CO 2 ] on 25 variables describing soybean physiology, growth and yield are reviewed using meta‐analytic techniques. This is the first meta‐analysis to our knowledge performed on a single crop species and summarizes the effects of 111 studies. These primary studies include numerous soybean growth forms, various stress and experimental treatments, and a range of elevated [CO 2 ] levels (from 450 to 1250 p.p.m.), with a mean of 689 p.p.m. across all studies. Stimulation of soybean leaf CO 2 assimilation rate with growth at elevated [CO 2 ] was 39%, despite a 40% decrease in stomatal conductance and a 11% decrease in Rubisco activity. Increased leaf CO 2 uptake combined with an 18% stimulation in leaf area to provide a 59% increase in canopy photosynthetic rate. The increase in total dry weight was lower at 37%, and seed yield still lower at 24%. This shows that even in an agronomic species selected for maximum investment in seed, several plant level feedbacks prevent additional investment in reproduction, such that yield fails to reflect fully the increase in whole plant carbon uptake. Large soil containers (> 9 L) have been considered adequate for assessing plant responses to elevated [CO 2 ]. However, in open‐top chamber experiments, soybeans grown in large pots showed a significant threefold smaller stimulation in yield than soybeans grown in the ground. This suggests that conclusions about plant yield based on pot studies, even when using very large containers, are a poor reflection of performance in the absence of any physical restriction on root growth. This review supports a number of current paradigms of plant responses to elevated [CO 2 ]. Namely, stimulation of photosynthesis is greater in plants that fix N and have additional carbohydrate sinks in nodules. This supports the notion that photosynthetic capacity decreases when plants are N‐limited, but not when plants have adequate N and sink strength. The root : shoot ratio did not change with growth at elevated [CO 2 ], sustaining the charge that biomass allocation is unaffected by growth at elevated [CO 2 ] when plant size and ontogeny are considered.

Changes in myofibrillar structure and function produced by N-terminal deletion of the regulatory light chain in Drosophila - Thomas Irving; Sanjoy Bhattacharya; Ivan Tesic; Jeff Moore; Gerrie Farman; Amanda Simcox; Jim Vigoreaux; David Maughan (Journal of Muscle Research and Cell Motility, 2001)

Phytoplankton distribution and survival in the thermocline - Jonathan Sharples; Mark C. Moore; Tom P. Rippeth; Patrick M. Holligan; David J. Hydes; Neil R. Fisher; John H. Simpson (Limnology and Oceanography, 2001)
Observations of the vertical structure of density, concentrations of chlorophyll a and nitrate, and turbulent dissipation rates were made over a period of 25 h in a well‐stratified shelf region in the Western English Channel, between neap and spring tides. Maximum turbulent dissipation at the base of the thermocline occurred almost 5 h after maximum tidal currents. This turbulence aids phytoplankton growth by supplying bottom‐layer nutrients into the subsurface chlorophyll maximum but reduces phytoplankton concentrations in the thermocline by mixing cells from the base of the subsurface maximum into the bottom mixed layer. The turbulent dissipation observations were used to estimate an average nitrate flux into the thermocline of 2.0 (0.8‐3.2, 95% confidence interval) mmol m −2 d −1 , which is estimated to have been capable of supporting new phytoplankton growth at a rate of 160 (64–256) mg C m −2 d −1 . Turbulent entrainment of carbon from the base of the subsurface biomass maximum into the bottom mixed layer was observed to be 290 (120–480) mg C m −2 d −1 . This apparent excess export from the chlorophyll maximum is suggested to be a feature of the spring‐neap cycle, with export dominating as the tidal turbulence increases toward spring tides and erodes the base of the thermocline. The observed rate of carbon export into the bottom mixed layer could account for as much as 25% of the gross annual primary production in stratifying shelf seas. Such turbulent losses, combined with grazing losses and low light levels, suggest that phytoplankton need to be highly adapted to environmental conditions within the thermocline in order to survive.

Formation of submarine flat-topped volcanic cones in Hawai'i - David A. Clague; James G. Moore; Jennifer R. Reynolds (Bulletin of Volcanology, 2000)

Synthetic peptides induce antibodies in sheep againstTaenia ovis - Davina L. Dadley-Moore; Marshall W. Lightowlers; Charles G. Gauci; James S. Rothel; David C. Jackson (International Journal of Peptide Research and Therapeutics, 1999)

Hybrid GPS + GLONASS - Alan H. Dodson; Terry Moore; David F. Baker; John W. Swann (GPS Solutions, 1999)

Physical constraints of chemoreception in foraging copepods - Paul A. Moore; David M. Fields; Jeannette Yen (Limnology and Oceanography, 1999)
The small‐scale spatial and temporal dynamics of phycosphere‐sized chemical signals entrained within the feeding current of copepods is quantified here by combining flow visualization techniques with electrochemical technology (IVEC‐10). Using the 30‐ μ m electrochemical probe sampling at 50 Hz and the velocity gradients created by two marine copepods, we evaluated how odor deformation improves the potential for remote chemoreception. Our data show that when shear is strong, as found in the feeding current of an omnivore, Pleuromamma xiphias , elongation of the chemical signal is greater than that found for an odor signal entrained in the low‐shear feeding current of a carnivore, Euchaeta rimana . Furthermore, within the feeding current of a single species, E. rimana , certain areas provided greater potential for remote chemoreception. These results support the hypotheses that chemical signals are deformed by the feeding current and that the feeding current structure enhances signal detection. The deformation of the odor field within the laminar feeding current provides a leading edge that gives a chemosensitive copepod early warning of an approaching odor source. By sensing the leading edge, a copepod could have a few hundred milliseconds to reorient itself with respect to the odor source. Advance warning improves the probability of successful behavior in response to signal sources such as prey, predators, and mates.

Regional variation in modern radiocarbon ages and the hard-water effects in Lakes Michigan and Huron - T.C. Moore; David K. Rea; Holly Godsey (Journal of Paleolimnology, 1998)

SEASONAL VARIATION IN RECEPTION OF FIN WHALE CALLS AT FIVE GEOGRAPHIC AREAS IN THE NORTH PACIFIC - Sue E. Moore; Kathleen M. Stafford; Marilyn E. Dahlheim; Christopher G. Fox; Howard W. Braham; Jeffrey J. Polovina; David E. Bain (Marine Mammal Science, 1998)

Simple calculation of the velocity profiles for pulsatile flow in a blood vessel using mathematica - Xiaoyi He; David N. Ku; James E. Moore (Annals of Biomedical Engineering, 1993)

Mechanism of soman-induced contractions in canine tracheal smooth muscle - Michael Adler; David H. Moore; Margaret G. Filbert (Archives of Toxicology, 1992)

Geochemical Processes Occurring in the Waters at the Amazon River/Ocean Boundary - David DeMaster; Brent McKee; Willard Moore; David Nelson; Williams Showers; Walker Smith (Oceanography, 1991)

Food sharing by sibling vs nonsibling spiny mice (Acomys cahirinus) - Richard H. Porter; John D. Moore; David M. White (Behavioral Ecology and Sociobiology, 1981)

Distribution of heavy metals and radionuclides in sediments, water, and fish in an area of Great Bear Lake contaminated with mine wastes - James W. Moore; David J. Sutherland (Archives of Environmental Contamination and Toxicology, 1981)

Biochemical and genetic characterization of kynurenine formamidase from Drosophila melanogaster - Gordon Paul Moore; David T. Sullivan (Biochemical Genetics, 1978)